Glass, glass plate, and method for producing glass plate
A glass substrate with specific oxide ratios addresses low dielectric loss, chemical resistance, and moisture resistance issues, ensuring effective signal transmission and substrate integrity in high-frequency devices.
Patent Information
- Application Number
- CN202380037678.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-09
- Filing Date
- 2023-04-28
- Publication Date
- 2024-12-17
AI Technical Summary
Existing glass substrates for high-frequency devices face challenges in achieving low dielectric loss tangent, chemical resistance, and moisture resistance, which affect signal transmission and substrate integrity during manufacturing and use.
A glass composition with specific oxide ratios, including SiO2 > 68%, Al2O3 0.1-8%, [SiO2]+[B2O3] > 88%, [B2O3]-([RO]+[R2O]-[Al2O3]) < 27%, and controlled relative dielectric constant and dielectric loss tangent, along with moisture resistance evaluation, to enhance chemical and moisture resistance.
The glass exhibits low dielectric loss tangent, excellent chemical resistance, and moisture resistance, reducing transmission loss and maintaining substrate integrity under high humidity and chemical cleaning conditions.
Smart Images

Figure CN119156354A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to glass, a glass plate and a method for producing the same which are suitable for a glass substrate for high-frequency devices, a panel-type antenna, a window glass, a vehicle window glass, a display panel and the like. Background Art
[0002] There are electronic devices such as mobile phones, smart phones, portable information terminals, Wi-Fi devices, communication devices, surface acoustic wave (SAW) devices, radar components, antenna components, etc. In such electronic devices, in order to achieve large communication capacity and high communication speed, the signal frequency is constantly being pushed to a higher frequency. The circuit substrates used in electronic devices for high-frequency purposes generally use insulating substrates such as resin substrates, ceramic substrates, and glass substrates. For insulating substrates used in high-frequency devices, in order to ensure the quality, strength and other characteristics of high-frequency signals, it is required to reduce transmission losses based on dielectric loss or conductor loss.
[0003] Among these insulating substrates, resin substrates have low rigidity due to their characteristics. Therefore, resin substrates are difficult to use when semiconductor packaging products require rigidity (strength). Ceramic substrates are difficult to improve the smoothness of the surface, and thus have the difficulty that the conductor loss caused by the conductor formed on the surface of the substrate tends to increase. On the other hand, glass substrates have the following characteristics: due to their high rigidity, it is easy to achieve miniaturization and thinning of the package, the surface smoothness is also excellent, and the substrate itself is easy to enlarge.
[0004] Patent Document 1 discloses a glass substrate for high-frequency devices having a dielectric loss tangent of 0.007 or less at a frequency of 35 GHz.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2018 / 051793 Summary of the invention
[0008] In recent years, in addition to the requirement to reduce the dielectric loss tangent in the high-frequency region, the glass substrates for the above-mentioned purposes are also required to have excellent chemical resistance. In the manufacturing process of the circuit substrates of liquid crystal antennas, high-frequency devices, etc., chemical cleaning is performed as a pretreatment for forming a wiring layer on the glass substrate. If the chemical resistance of the glass is low, for example, during acid cleaning, the substrate surface dissolves, the smoothness of the substrate surface is impaired, and the adhesion of the film formed on the substrate surface may decrease. In addition, the dissolved matter may also adhere to the substrate surface. As a result, the conductor loss caused by the conductor formed on the substrate surface may increase.
[0009] In addition, the glass substrate for the above-mentioned purpose requires excellent moisture resistance. If the moisture resistance is low, the substrate surface deteriorates during storage, and the smoothness of the substrate surface may be impaired. In addition, by having excellent moisture resistance, it can also withstand use under high humidity.
[0010] An object of the present invention is to provide glass having a low dielectric loss tangent in a high frequency region and excellent chemical resistance and moisture resistance.
[0011] The present inventors have found that the above-mentioned problems can be solved by setting the glass composition to a specific range, while reducing dielectric loss and improving chemical resistance and moisture resistance, thereby completing the present invention.
[0012] [1] A glass expressed in mole % based on oxides,
[0013] SiO2 is more than 68%,
[0014] Al2O3 is 0.1~8%,
[0015] [SiO2]+[B2O3] is more than 88%,
[0016] [B2O3]-([RO]+[R2O]-[Al2O3]) is less than 27%,
[0017] The relative dielectric constant at 25°C and 10 GHz is less than 4.5.
[0018] The dielectric loss tangent at 25°C and 10 GHz is less than 0.005.
[0019] ΔAbs-OH calculated by the following method is 4.0 or less,
[0020] SrO is 0.1-4%,
[0021] The total content (RO) of MgO, CaO, SrO and BaO is greater than 0% and less than 6%, and the total content (R2O) of Li2O, Na2O and K2O is 0-1%.
[0022] [Al2O3]-[RO] is greater than -3% and less than 8%,
[0023] [Al2O3]×[RO] is greater than 0 and less than 30,
[0024] [MgO] + [CaO] is 0.1 to 5.9%,
[0025] [MgO] / ([MgO]+[Al2O3]) is 0 to 0.45.
[0026] [ ] indicates the content of the component in parentheses expressed in mol % based on oxides.
[0027] The above method is as follows: glass is made into a glass plate with a thickness of 0.45 to 0.75 mm, and after measuring Abs-OH, the glass plate is left to stand at a temperature of 60°C and a relative humidity of 95%. Abs-OH of the glass plate is measured 90 hours after the start of standing. The value obtained by subtracting Abs-OH before standing from Abs-OH after standing is calculated as ΔAbs-OH.
[0028] [2] A glass, expressed as mol% based on oxides,
[0029] SiO2 is more than 68%,
[0030] Al2O3 is 0.1~8%,
[0031] [SiO2]+[B2O3] is more than 88%,
[0032] [B2O3]-([RO]+[R2O]-[Al2O3]) is less than 27%,
[0033] The relative dielectric constant at 25°C and 10 GHz is less than 4.5.
[0034] The dielectric loss tangent at 25°C and 10 GHz is less than 0.005.
[0035] ΔAbs-OH calculated by the following method is 4.0 or less,
[0036] CaO is 0.1-6%,
[0037] The total content (RO) of MgO, CaO, SrO and BaO is greater than 0% and less than 6%, and the total content (R2O) of Li2O, Na2O and K2O is 0-1%.
[0038] [Al2O3]-[RO] is greater than -3% and less than 8%,
[0039] [Al2O3]×[RO] is greater than 0 and less than 28,
[0040] (([MgO]+[CaO])-([SrO]+[BaO])) / [Al2O3] is -3.0 to 0.60.
[0041] [ ] indicates the content of the component in parentheses expressed in mol % based on oxides.
[0042] The above method is as follows: glass is made into a glass plate with a thickness of 0.45 to 0.75 mm, and after measuring Abs-OH, the glass plate is left to stand at a temperature of 60°C and a relative humidity of 95%. Abs-OH of the glass plate is measured 90 hours after the start of standing. The value obtained by subtracting Abs-OH before standing from Abs-OH after standing is calculated as ΔAbs-OH.
[0043] [3] A glass, expressed as mol% based on oxides,
[0044] SiO2 is more than 68%,
[0045] Al2O3 is 0.1~8%,
[0046] [SiO2]+[B2O3] is more than 88%,
[0047] [B2O3]-([RO]+[R2O]-[Al2O3]) is less than 27%,
[0048] The relative dielectric constant at 25°C and 10 GHz is less than 4.5.
[0049] The dielectric loss tangent at 25°C and 10 GHz is less than 0.005.
[0050] ΔAbs-OH calculated by the following method is 4.0 or less,
[0051] Li2O is greater than 0%,
[0052] K2O is greater than 0% and less than 0.8%,
[0053] The total content of MgO, CaO, SrO and BaO (RO) is 0-0.5%,
[0054] The total content of Li2O, Na2O and K2O (R2O) is greater than 0% and less than 4%,
[0055] [Al2O3]×[R2O] is greater than 0 and less than 1.40,
[0056] [Na2O] / [R2O] is 0.30 to 0.99.
[0057] [ ] indicates the content of the component in parentheses expressed in mol % based on oxides.
[0058] The above method is as follows: glass is made into a glass plate with a thickness of 0.45 to 0.75 mm, and after measuring Abs-OH, the glass plate is left to stand at a temperature of 60°C and a relative humidity of 95%. Abs-OH of the glass plate is measured 90 hours after the start of standing. The value obtained by subtracting Abs-OH before standing from Abs-OH after standing is calculated as ΔAbs-OH.
[0059] [4] The glass according to any one of [1] to [3], wherein the acid resistance calculated by the following method is 0.05 mg / cm 2 Below, alkali resistance is 0.15mg / cm 2 the following.
[0060] The acid resistance evaluation method is as follows: the glass is made into a glass plate with a side of 31 to 36 mm and a thickness of 0.45 to 0.75 mm, the glass sample is immersed in an acid aqueous solution (a 45° C. aqueous solution containing 7.7 mass % HNO3 and 6.5 mass % H2SO4) for 170 seconds, and the amount of glass component dissolved per unit surface area (mg / cm 2 ) as acid resistance.
[0061] The alkali resistance evaluation method is as follows: the glass is formed into a glass plate with a side of 31 to 36 mm and a thickness of 0.45 to 0.75 mm, the glass sample is immersed in an alkaline aqueous solution (a 60° C. aqueous solution containing 1.2 mass % KOH) for 30 minutes, and the amount of glass component dissolved per unit surface area (mg / cm 2 ) as alkali resistance.
[0062] [5] The glass according to any one of [1] to [4], which contains 0.01% or more of Cl, expressed as mol% based on oxides.
[0063] [6] The glass according to any one of [1] to [5], wherein Abs—OH is 0.1 to 10.0.
[0064] [7] The glass according to any one of [1] to [6], wherein the average thermal expansion coefficient at 50 to 350° C. is 20×10 -7 / K~50×10 -7 / K.
[0065] [8] The glass according to any one of [1] to [7], wherein the glass transition temperature is 750° C. or lower.
[0066] [9] A glass plate comprising the glass according to any one of [1] to [8] and having an impregnation condition, wherein the glass plate has a thickness of not more than 0.75 mm.
[0067]
[10] A method for producing a glass plate, comprising producing the glass according to any one of [1] to [8] by a float process or a fusion process.
[0068]
[11] A glass substrate comprising the glass according to any one of [1] to [8], the glass substrate being used for a high-frequency device that processes a high-frequency signal of 10 GHz or higher.
[0069]
[12] A glass substrate comprising the glass described in any one of [1] to [8],
[0070] A wiring layer is formed on the glass substrate.
[0071] The glass of the present invention has a low dielectric loss tangent in the high frequency region. Therefore, the dielectric loss of high frequency signals can be reduced, and the glass substrate is suitable for high frequency devices. According to the circuit substrate using such a glass substrate, the transmission loss of high frequency signals can be reduced, and practical high frequency devices such as electronic devices can be provided.
[0072] The glass of the present invention has excellent chemical resistance. Therefore, when the glass substrate is acid-cleaned in the manufacturing process of the circuit substrate of the liquid crystal antenna, high-frequency device, etc., there is no worry that the substrate surface will dissolve and the smoothness of the substrate surface will deteriorate, or that the dissolved matter will adhere to the substrate surface. Therefore, it is possible to prevent the adhesion of the film formed on the substrate surface from decreasing. In addition, it is possible to prevent the conductor loss from increasing.
[0073] The glass of the present invention can reduce the transmission loss of radio waves in a high-frequency band, and is therefore also suitable for glass products that transmit and receive radio waves in a high-frequency band.
[0074] The glass of the present invention has excellent moisture resistance, and thus can be prevented from deteriorating during storage. In addition, the glass is suitable for use under high temperature and high humidity conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0075] Figure 1 It is a schematic cross-sectional view showing an example of the structure of a circuit board for a high-frequency device.
[0076] Figure 2 It is a graph showing the relationship between [B2O3]-([RO]+[R2O]-[Al2O3]) and ΔAbs-OH.
[0077] Figure 3 This is a graph showing the relationship between Cl and Abs-OH in Examples 13 to 16.
[0078] Figure 4 This is a graph showing the relationship between Abs-OH in Examples 13 to 16 and the relative dielectric constant and dielectric loss tangent at a frequency of 10 GHz. DETAILED DESCRIPTION
[0079] Hereinafter, embodiments of the present invention will be described.
[0080] The present invention provides a glass (hereinafter referred to as "glass according to a first embodiment")
[0081] Expressed as mol % based on oxide,
[0082] SiO2 is more than 68%,
[0083] Al2O3 is 0.1~8%,
[0084] [SiO2]+[B2O3] is more than 88%,
[0085] [B2O3]-([RO]+[R2O]-[Al2O3]) is less than 27%,
[0086] The relative dielectric constant at 25°C and 10 GHz is less than 4.5.
[0087] The dielectric loss tangent at 25°C and 10 GHz is less than 0.005.
[0088] ΔAbs-OH is less than 4.0,
[0089] SrO is 0.1-4%,
[0090] The total content (RO) of MgO, CaO, SrO and BaO is greater than 0% and less than 6%, and the total content (R2O) of Li2O, Na2O and K2O is 0-1%.
[0091] [Al2O3]-[RO] is greater than -3% and less than 8%,
[0092] [Al2O3]×[RO] is greater than 0 and less than 30,
[0093] [MgO] + [CaO] is 0.1 to 5.9%,
[0094] [MgO] / ([MgO]+[Al2O3]) is 0 to 0.45.
[0095] Furthermore, the present invention provides a glass (hereinafter referred to as "glass according to the second embodiment")
[0096] Expressed as mol % based on oxide,
[0097] SiO2 is more than 68%,
[0098] Al2O3 is 0.1~8%,
[0099] [SiO2]+[B2O3] is more than 88%,
[0100] [B2O3]-([RO]+[R2O]-[Al2O3]) is less than 27%,
[0101] The relative dielectric constant at 25°C and 10 GHz is less than 4.5.
[0102] The dielectric loss tangent at 25°C and 10 GHz is less than 0.005.
[0103] ΔAbs-OH is less than 4.0,
[0104] CaO is 0.1-6%,
[0105] The total content (RO) of MgO, CaO, SrO and BaO is greater than 0% and less than 6%, and the total content (R2O) of Li2O, Na2O and K2O is 0-1%.
[0106] [Al2O3]-[RO] is greater than -3% and less than 8%,
[0107] [Al2O3]×[RO] is greater than 0 and less than 28,
[0108] (([MgO]+[CaO])-([SrO]+[BaO])) / [Al2O3] is -3.0 to 0.60.
[0109] Furthermore, the present invention provides a glass (hereinafter referred to as "glass according to the third embodiment")
[0110] Expressed as mol % based on oxide,
[0111] SiO2 is more than 68%,
[0112] Al2O3 is 0.1~8%,
[0113] [SiO2]+[B2O3] is more than 88%,
[0114] [B2O3]-([RO]+[R2O]-[Al2O3]) is less than 27%,
[0115] The relative dielectric constant at 25°C and 10 GHz is less than 4.5.
[0116] The dielectric loss tangent at 25°C and 10 GHz is less than 0.005.
[0117] ΔAbs-OH is less than 4.0,
[0118] Li2O is greater than 0%,
[0119] K2O is greater than 0% and less than 0.8%,
[0120] The total content of MgO, CaO, SrO and BaO (RO) is 0-0.5%,
[0121] The total content of Li2O, Na2O and K2O (R2O) is greater than 0% and less than 4%,
[0122] [Al2O3]×[R2O] is greater than 0 and less than 1.40,
[0123] [Na2O] / [R2O] is 0.30 to 0.99.
[0124] In this specification, "the glass of the present invention" includes the glass of the first embodiment, the glass of the second embodiment, and the glass of the third embodiment. In the glasses of the first to third embodiments, [] in each formula represents the content of the component described in parentheses expressed in mol % based on oxides.
[0125] It should be noted that in the following description, the numerical range represented by "to" indicates a range including the numerical values recorded before and after "to" as the minimum and maximum values, respectively. The content of each component in glass or a glass plate is expressed as a molar percentage (mol %) based on an oxide, and is also simply expressed as "%" unless otherwise specified.
[0126] It should be noted that "high frequency" in this specification means a frequency of 10 GHz or more, preferably greater than 30 GHz, more preferably 35 GHz or more. In addition, high frequency means a frequency of 3 THz or less, preferably 1 THz or less, more preferably 300 GHz or less, and further preferably 100 GHz or less.
[0127] Hereinafter, as specific embodiments of the glass of the present invention (hereinafter, sometimes simply referred to as “glass”), glasses according to first to third embodiments will be described.
[0128] [Common structure of the glasses of the first to third embodiments]
[0129] The glasses of the first to third embodiments, that is, the glasses of the present invention, have the following structures.
[0130] Expressed as mol % based on oxide,
[0131] SiO2 is more than 68%,
[0132] Al2O3 is 0.1~8%,
[0133] [SiO2]+[B2O3] is more than 88%,
[0134] [B2O3]-([RO]+[R2O]-[Al2O3]) is less than 27%,
[0135] The relative dielectric constant at 25°C and 10 GHz is less than 4.5.
[0136] The dielectric loss tangent at 25°C and 10 GHz is less than 0.005.
[0137] ΔAbs-OH calculated by the following method is 4.0 or less.
[0138] Method: The glass is made into a glass plate with a thickness of 0.45 to 0.75 mm. After measuring Abs-OH, the glass plate is left to stand at a temperature of 60°C and a relative humidity of 95%. The Abs-OH of the glass plate is measured 90 hours after the start of standing. The value obtained by subtracting the Abs-OH before standing from the Abs-OH after standing is calculated as ΔAbs-OH.
[0139] Hereinafter, the common structure of the glass of the present invention will be described in detail.
[0140] SiO2 is a network-forming substance. The glass of the present invention contains more than 68% SiO2. If the content of SiO2 is more than 68%, the dielectric loss tangent in the high-frequency region can be reduced, the glass forming ability and chemical resistance can be improved, and the rise in the surface devitrification temperature can be suppressed. In the glass of the present invention, the content of SiO2 is preferably more than 68.3%, more preferably more than 68.5%, further preferably more than 68.8%, further preferably more than 69.1%, further preferably more than 69.4%, particularly more preferably more than 69.7%, more preferably more than 70.0%, further more preferably more than 70.2%, further more preferably more than 70.4%, further more preferably more than 70.5%, further more preferably more than 70.7%, and particularly more preferably more than 70.9%.
[0141] In addition, in the glass of the present invention, the content of SiO2 is preferably 85% or less. If the content of SiO2 is 85% or less, the solubility of the glass can be improved. The content of SiO2 is more preferably 84% or less, further preferably 83% or less, further preferably 82% or less, further preferably 81% or less, particularly further preferably 80% or less, further preferably 79.5% or less, further more preferably 79.0% or less, further more preferably 78.5% or less, further more preferably 78.0% or less, further more preferably 77.5% or less, and particularly further more preferably 77.0% or less.
[0142] The glass of the present invention contains 0.1 to 8% Al2O3. Al2O3 is a component that has effects on improving chemical resistance, improving Young's modulus, improving the phase separation characteristics of glass, reducing thermal expansion coefficient, etc. If the content of Al2O3 is 0.1% or more, the chemical resistance and phase separation characteristics of the glass are improved. The content of Al2O3 is preferably 0.13% or more, more preferably 0.16% or more, further preferably 0.19% or more, further preferably 0.22% or more, further preferably 0.25% or more, particularly further preferably 0.28% or more, more preferably 0.31% or more, further preferably 0.34% or more, further preferably 0.37% or more, further more preferably 0.4% or more, further more preferably 0.43% or more, and particularly further more preferably 0.46% or more.
[0143] In addition, in the glass of the present invention, if the Al2O3 content is 8% or less, the dielectric loss tangent in the high frequency region can be reduced. The Al2O3 content is preferably 7.5% or less, more preferably 7.0% or less, further preferably 6.8% or less, further preferably 6.6% or less, further preferably 6.4% or less, particularly further preferably 6.2% or less, further preferably 6.0% or less, further more preferably 5.8% or less, further more preferably 5.6% or less, further more preferably 5.4% or less, further more preferably 5.2% or less, and particularly further more preferably 5% or less.
[0144] In the glass of the present invention, the total content of SiO2 and B2O3 ([SiO2] + [B2O3]) is 88% or more. If [SiO2] + [B2O3] is 88% or more, the dielectric properties are improved. In the glass of the present invention, [SiO2] + [B2O3] is more preferably 88.3% or more, further preferably 88.6% or more, further preferably 88.9% or more, particularly preferably 89.2% or more, further preferably 89.5% or more, further preferably 89.8% or more, further preferably 90.1% or more, further more preferably 90.4% or more, further more preferably 90.7% or more, and particularly further more preferably 91% or more.
[0145] In the glass of the present invention, [SiO2]+[B2O3] is preferably 99% or less. In the glass of the present invention, [SiO2]+[B2O3] is more preferably 98.8% or less, further preferably 98.6% or less, further preferably 98.4% or less, still further preferably 98.2% or less, particularly further preferably 98.1% or less, still more preferably 98% or less, still more preferably 97.9% or less, further more preferably 97.8% or less, further more preferably 97.7% or less, still further more preferably 97.6% or less, and particularly further more preferably 97.5% or less.
[0146] In the glass of the present invention, [B2O3]-([RO]+[R2O]-[Al2O3]) is 27% or less. The smaller the value of [B2O3]-([RO]+[R2O]-[Al2O3]), the higher the moisture resistance of the glass. Therefore, in the glass of the present invention, [B2O3]-([RO]+[R2O]-[Al2O3]) is 27% or less, preferably 26.8% or less, more preferably 26.6% or less, further preferably 26.4% or less, further preferably 26.2% or less, further preferably 26% or less, particularly further preferably 25.8% or less, more preferably 25.6% or less, further preferably 25.4% or less, further more preferably 25.3% or less, further more preferably 25.2% or less, further more preferably 25.1% or less, and particularly further more preferably 25% or less.
[0147] In the glass of the present invention, from the viewpoint of dielectric properties, [B2O3]-([RO]+[R2O]-[Al2O3]) is preferably 15% or more. [B2O3]-([RO]+[R2O]-[Al2O3]) is more preferably 16% or more, further preferably 16.3% or more, further preferably 16.6% or more, still further preferably 16.9% or more, particularly further preferably 17.2% or more, still more preferably 17.5% or more, still more preferably 17.8% or more, further more preferably 18.1% or more, further more preferably 18.4% or more, further more preferably 18.7% or more, and particularly further more preferably 19% or more.
[0148] The glass of the present invention has a ΔAbs-OH calculated by the following method of 4.0 or less.
[0149] When ΔAbs-OH is 4.0 or less, the glass exhibits excellent moisture resistance. ΔAbs-OH is preferably 3.5 or less, more preferably 3.0 or less, and further preferably 2.5 or less. The lower limit of ΔAbs-OH is not particularly limited, and ΔAbs-OH is preferably 0 or more, for example.
[0150] Method: The glass is made into a glass plate with a thickness of 0.45 to 0.75 mm. After measuring Abs-OH, the glass plate is left to stand at a temperature of 60°C and a relative humidity of 95%. The Abs-OH of the glass plate is measured 90 hours after the start of standing. The value obtained by subtracting the Abs-OH before standing from the Abs-OH after standing is calculated as ΔAbs-OH.
[0151] The Δ(Abs β-OH -Abs Base ) is an index of moisture resistance that is not easily affected by the thickness of the glass plate during measurement. β-OH -Abs Base ) is preferably less than 0.2.
[0152] Method: Make the glass into glass plates with a thickness of 0.45 to 0.75 mm and measure (Abs β-OH -Abs Base ) and then the glass plate was left to stand at a temperature of 60°C and a relative humidity of 95%. 90 hours after the start of the standing, the glass plate (Abs β-OH -Abs Base ) Calculate the value of (Abs β-OH -Abs Base ) minus the value before resting (Abs β-OH -Abs Base ) is taken as Δ(Abs β-OH -Abs Base ).
[0153] If Δ(Abs β-OH -Abs Base ) is 0.2 or less, the glass exhibits excellent moisture resistance. β-OH -Abs Base ) is preferably 0.15 or less, more preferably 0.12 or less, further preferably 0.1 or less, and particularly preferably 0.05 or less. Δ(Abs β-OH -Abs Base ) is not particularly limited, Δ(Abs β-OH -Abs Base ) is preferably greater than 0, for example.
[0154] The dielectric loss tangent of the glass of the present invention at 20°C and 10 GHz is 0.005 or less. If the dielectric loss tangent at 20°C and a frequency of 10 GHz is 0.005 or less, the dielectric loss in the high frequency region exceeding the frequency of 10 GHz can be reduced. The dielectric loss tangent at 20°C and 10 GHz is preferably 0.0045 or less, more preferably 0.0040 or less, further preferably 0.0035 or less, further preferably 0.0030 or less, and further preferably 0.0025 or less. The lower limit is not particularly limited, for example, preferably 0.0001 or more.
[0155] The relative dielectric constant of the glass of the present invention at 20°C and a frequency of 10 GHz is 4.5 or less. If the relative dielectric constant at a frequency of 10 GHz is 4.5 or less, the dielectric loss in the high frequency region can be reduced. The relative dielectric constant at 20°C and a frequency of 10 GHz is preferably 4.45 or less, more preferably 4.40 or less, further preferably 4.35 or less, further preferably 4.30 or less, further preferably 4.25 or less, particularly further preferably 4.20 or less, further preferably 4.15 or less, and further preferably 4.10 or less. The lower limit is not particularly limited, for example, preferably 3 or more.
[0156] The glass of the present invention has the above-mentioned common structure and thus exhibits a low dielectric loss tangent in a high frequency region and excellent chemical resistance and moisture resistance.
[0157] [Glass of the first embodiment]
[0158] The glass of the first embodiment has the following structure in addition to the above-mentioned common structure, especially from the viewpoint of further improving solubility, chemical resistance, phase separation characteristics and dielectric properties, and suppressing an increase in surface devitrification temperature.
[0159] Expressed as mol % based on oxide,
[0160] SrO is 0.1-4%,
[0161] The total content (RO) of MgO, CaO, SrO and BaO is greater than 0% and less than 6%, and the total content (R2O) of Li2O, Na2O and K2O is 0-1%.
[0162] [Al2O3]-[RO] is greater than -3% and less than 8%,
[0163] [Al2O3]×[RO] is greater than 0 and less than 30,
[0164] [MgO] + [CaO] is 0.1 to 5.9%,
[0165] [MgO] / ([MgO]+[Al2O3]) is 0 to 0.45.
[0166] Hereinafter, the above-mentioned configuration will be described in detail.
[0167] SrO is a component that improves the moisture resistance of glass, does not increase the surface devitrification temperature, and improves solubility. The glass of the first embodiment contains 0.1 to 4% SrO. In the glass of the first embodiment, if the content of SrO is 0.1% or more, the moisture resistance is improved, the surface devitrification temperature is not increased, and the solubility is improved.
[0168] In the glass of the first embodiment, the SrO content is preferably 0.2% or more, more preferably 0.3% or more, further preferably 0.4% or more, further preferably 0.5% or more, still further preferably 0.6% or more, particularly further preferably 0.7% or more, even more preferably 0.8% or more, still more preferably 0.9% or more, further more preferably 1% or more, further more preferably 1.1% or more, still further more preferably 1.2% or more, and particularly further more preferably 1.3% or more.
[0169] In the glass of the first embodiment, if the content of SrO is 4% or less, deterioration of chemical resistance can be suppressed, and further, without making the specific gravity too large, the average thermal expansion coefficient can be suppressed from being too high. In the glass of the first embodiment, the content of SrO is preferably 3.8% or less, more preferably 3.6% or less, further preferably 3.4% or less, further preferably 3.2% or less, further preferably 3% or less, particularly further preferably 2.8% or less, further preferably 2.6% or less, further preferably 2.4% or less, further more preferably 2.2% or less, further more preferably 2.0% or less, further more preferably 1.8% or less, and particularly further more preferably 1.6% or less.
[0170] MgO, CaO, SrO and BaO are components that suppress the rise of the surface devitrification temperature and improve the solubility. In the glass of the first embodiment, the total content (RO) of MgO, CaO, SrO and BaO is greater than 0% and is less than 6%. In the glass of the first embodiment, by RO being greater than 0%, the rise of the surface devitrification temperature is suppressed and the solubility is improved. In the glass of the first embodiment, RO is preferably 0.1% or more, more preferably 0.3% or more, further preferably 0.5% or more, particularly further preferably 0.7% or more, more preferably 0.9% or more, further more preferably 1.1% or more, further more preferably 1.3% or more, further more preferably 1.5% or more, further more preferably 1.7% or more, and particularly further more preferably 1.9% or more.
[0171] In the glass of the first embodiment, when RO is 6% or less, dielectric properties and chemical resistance are improved. In the glass of the first embodiment, RO is preferably 5.8% or less, more preferably 5.6% or less, further preferably 5.4% or less, further preferably 5.2% or less, still further preferably 5% or less, particularly further preferably 4.8% or less, still more preferably 4.6% or less, still further preferably 4.4% or less, further further preferably 4.3% or less, further further preferably 4.2% or less, further further preferably 4.1% or less, and particularly further preferably 4% or less.
[0172] Li2O, Na2O and K2O are components that improve moisture resistance and solubility. In addition, they have the effect of suppressing the rise of surface devitrification temperature and improving the average thermal expansion coefficient. In the glass of the first embodiment, the total content (R2O) of Li2O, Na2O and K2O is 0-1%. In the glass of the first embodiment, by containing Li2O, Na2O and K2O, moisture resistance and solubility can be improved. In the glass of the first embodiment, when containing Li2O, Na2O and K2O, R2O is preferably 0.1% or more, more preferably 0.2% or more, further preferably 0.3% or more, further preferably 0.4% or more, and particularly preferably 0.5% or more.
[0173] In the glass of the first embodiment, the dielectric properties are improved by setting R2O to 1% or less. In the glass of the first embodiment, R2O is preferably 0.9% or less, more preferably 0.8% or less, further preferably 0.7% or less, further preferably 0.6% or less, and further preferably 0.5% or less.
[0174] In the glass of the first embodiment, [Al2O3]-[RO] is not less than -3% and less than 8%. In the glass of the first embodiment, the phase separation characteristics are improved by [Al2O3]-[RO] being not less than -3%. In the glass of the first embodiment, [Al2O3]-[RO] is preferably not less than -2.8%, more preferably not less than -2.6%, further preferably not less than -2.4%, further preferably not less than -2.2%, further preferably not less than -2%, particularly further preferably not less than -1.8%, further preferably not less than -1.6%, further preferably not less than -1.4%, further more preferably not less than -1.2%, further more preferably not less than -1%, further more preferably not less than -0.8%, and particularly further more preferably not less than -0.6%.
[0175] In the glass of the first embodiment, if [Al2O3]-[RO] is less than 8%, the solubility is improved and the increase in the surface devitrification temperature can be suppressed. In the glass of the first embodiment, [Al2O3]-[RO] is preferably 7.5% or less, more preferably 7% or less, further preferably 6.5% or less, further preferably 6% or less, further preferably 5.5% or less, particularly further preferably 5% or less, further preferably 4.7% or less, further preferably 4.4% or less, further more preferably 4.1% or less, further more preferably 3.8% or less, further more preferably 3.5% or less, and particularly further more preferably 3% or less.
[0176] In the glass of the first embodiment, [Al2O3]×[RO] is greater than 0 and is 30 or less. In the glass of the first embodiment, the phase separation characteristics can be improved by [Al2O3]×[RO] being greater than 0. In the glass of the first embodiment, [Al2O3]×[RO] is preferably 1 or more, more preferably 2 or more, further preferably 3 or more, further preferably 3.5 or more, further preferably 4 or more, particularly further preferably 4.5 or more, further preferably 5 or more, further more preferably 5.5 or less, further more preferably 6 or more, further more preferably 6.5 or more, further more preferably 7 or more, and particularly further more preferably 7.5 or more.
[0177] In the glass of the first embodiment, when [Al2O3]×[RO] is 30 or less, the dielectric properties can be improved. In the glass of the first embodiment, [Al2O3]×[RO] is preferably 29 or less, more preferably 28 or less, further preferably 27 or less, further preferably 26 or less, still further preferably 25 or less, particularly further preferably 24 or less, further preferably 23 or less, still further preferably 22 or less, further further preferably 21.5 or less, further further preferably 21 or less, further further preferably 20.5 or less, and particularly further preferably 20 or less.
[0178] In the glass of the first embodiment, the total content of MgO and CaO ([MgO] + [CaO]) is 0.1 to 5.9%. In the glass of the first embodiment, by making [MgO] + [CaO] 0.1% or more, effects such as improving solubility, improving moisture resistance, and suppressing the increase in surface devitrification temperature can be obtained.
[0179] In the glass of the first embodiment, [MgO] + [CaO] is preferably 0.2% or more, more preferably 0.4% or more, further preferably 0.6% or more, further preferably 0.8% or more, still further preferably 1% or more, particularly further preferably 1.2% or more, even more preferably 1.4% or more, still more preferably 1.6% or more, still more preferably 1.8% or more, still more preferably 2% or more, still more preferably 2.2% or more, and particularly further preferably 2.4% or more.
[0180] In the glass of the first embodiment, if [MgO] + [CaO] is 5.9% or less, deterioration of dielectric properties can be suppressed. In the glass of the first embodiment, [MgO] + [CaO] is preferably 5.8% or less, more preferably 5.6% or less, further preferably 5.4% or less, further preferably 5.2% or less, further preferably 5% or less, particularly further preferably 4.8% or less, further preferably 4.6% or less, further preferably 4.4% or less, further more preferably 4.2% or less, further more preferably 4% or less, further more preferably 3.8% or less, and particularly further more preferably 3.6% or less.
[0181] In the glass of the first embodiment, [MgO] / ([MgO]+[Al 2 O 3 ]) is 0 to 0.45.
[0182] In the glass of the first embodiment, [MgO] / ([MgO]+[Al2O3]) is preferably greater than 0, more preferably greater than 0.01, further preferably greater than 0.02, further preferably greater than 0.03, still further preferably greater than 0.04, particularly further preferably greater than 0.05, still more preferably greater than 0.06, still further preferably less than 0.07, further more preferably greater than 0.08, further more preferably greater than 0.09, still further more preferably greater than 0.1, and particularly further more preferably greater than 0.11.
[0183] In the glass of the first embodiment, the increase in the surface devitrification temperature can be suppressed by [MgO] / ([MgO]+[Al2O3]) being 0.45 or less. In the glass of the first embodiment, [MgO] / ([MgO]+[Al2O3]) is preferably 0.45 or less, more preferably 0.44 or less, further preferably 0.43 or less, further preferably 0.42 or less, still further preferably 0.41 or less, particularly further preferably 0.4 or less, further preferably 0.39 or less, still further preferably 0.35 or less, further further preferably 0.31 or less, further further preferably 0.3 or less, further further preferably 0.25 or less, and particularly further preferably 0.2 or less.
[0184] B2O3 is a component that reduces the dielectric loss tangent in the high-frequency region. The glass of the first embodiment preferably contains 15 to 30% of B2O3. In the glass of the first embodiment, by making the content of B2O3 15% or more, the solubility is improved. In addition, the dielectric loss tangent in the high-frequency region can be reduced. The content of B2O3 is more preferably 16% or more, further preferably 16.5% or more, further preferably 17% or more, further preferably 17.5% or more, and particularly preferably 18% or more.
[0185] In the glass of the first embodiment, if B2O3 is 30% or less, chemical resistance can be improved. The content of B2O3 is more preferably 29% or less, further preferably 28% or less, further preferably 27% or less, further preferably 26% or less, and particularly preferably 25% or less.
[0186] CaO is a component that has the characteristics of increasing the specific elastic modulus second only to MgO among alkaline earth metals without excessively lowering the strain point, and also improves solubility. Furthermore, it is a component that is less likely to deteriorate moisture resistance and less likely to increase the surface devitrification temperature than MgO. The glass of the first embodiment may contain CaO. In the glass of the first embodiment, by containing CaO, the average thermal expansion coefficient will not be too high, and the increase in the surface devitrification temperature can be suppressed. In the glass of the first embodiment, when CaO is contained, the CaO content is preferably 0.1% or more, more preferably 0.2% or more, further preferably 0.3% or more, further preferably 0.4% or more, further preferably 0.5% or more, and particularly preferably 0.6% or more.
[0187] In the glass of the first embodiment, from the viewpoint of not making the average thermal expansion coefficient too high and suppressing the increase in the surface devitrification temperature, the CaO content is preferably 4% or less, more preferably 3.8% or less, further preferably 3.6% or less, further preferably 3.4% or less, further preferably 3.2% or less, and particularly preferably 3% or less.
[0188] MgO is a component that increases Young's modulus without increasing specific gravity. That is, MgO is a component that increases the specific elastic modulus, thereby alleviating the problem of bending, increasing the fracture toughness value and increasing the strength of the glass. In addition, MgO is a component that also increases solubility. Therefore, the glass of the first embodiment may contain MgO.
[0189] In the glass of the first embodiment, when MgO is contained, the content of MgO is preferably 0.1% or more, more preferably 0.2% or more, further preferably 0.3% or more, further preferably 0.4% or more, further preferably 0.5% or more, and particularly further preferably 0.6% or more. In the glass of the first embodiment, from the viewpoint of suppressing the increase in the surface devitrification temperature, the content of MgO is preferably 4% or less, more preferably 3.8% or less, further preferably 3.6% or less, further preferably 3.4% or less, further preferably 3.2% or less, and particularly further preferably 3% or less.
[0190] BaO is a component that improves the moisture resistance of glass, does not increase the surface devitrification temperature, and improves solubility. In addition, it also has the effect of increasing the average thermal expansion coefficient. Therefore, the glass of the first embodiment may contain BaO. In the glass of the first embodiment, when BaO is contained, the content of BaO is preferably 0.1% or more, more preferably 0.2% or more, further preferably 0.3% or more, further preferably 0.4% or more, further preferably 0.5% or more, and particularly preferably 0.6% or more.
[0191] In the glass of the first embodiment, if a large amount of BaO is contained, the specific gravity tends to increase and the Young's modulus tends to decrease. In addition, the chemical resistance of the glass decreases. Therefore, in the glass of the first embodiment, the content of BaO is preferably 4% or less, more preferably 3.8% or less, further preferably 3.6% or less, further preferably 3.4% or less, further preferably 3.2% or less, and particularly preferably 3% or less.
[0192] Li2O is a component that improves moisture resistance and solubility. In addition, it also has the effect of suppressing the increase in surface devitrification temperature and increasing the average thermal expansion coefficient. The glass of the first embodiment may contain Li2O. In the glass of the first embodiment, when Li2O is contained, the content of Li2O is preferably 0.1% or more. By containing 0.01% or more of Li2O, the solubility is improved. In the glass of the first embodiment, the content of Li2O is more preferably 0.03% or more, further preferably 0.05% or more, further preferably 0.07% or more, further preferably 0.09% or more, and particularly preferably 0.1% or more.
[0193] In the glass of the first embodiment, from the viewpoint of dielectric properties, the content of Li2O is preferably 0.8% or less, more preferably 0.7% or less, further preferably 0.6% or less, further preferably 0.5% or less, further preferably 0.4% or less, and particularly preferably 0.3% or less.
[0194] K2O is a component that improves moisture resistance and solubility. In addition, it also has the effect of suppressing the rise of the surface devitrification temperature and improving the average thermal expansion coefficient. The glass of the first embodiment may contain K2O. In the glass of the first embodiment, by containing K2O, the solubility and phase separation characteristics are improved. In the glass of the first embodiment, when K2O is contained, the content of K2O is preferably 0.01% or more, more preferably 0.03% or more, further preferably 0.05% or more, further preferably 0.07% or more, further preferably 0.09% or more, and particularly preferably 0.1% or more.
[0195] In the glass of the first embodiment, from the viewpoint of dielectric properties, the content of K2O is preferably 0.5% or less, more preferably 0.4% or less, further preferably 0.3% or less, further preferably 0.25% or less, further preferably 0.2% or less, and particularly preferably 0.15% or less.
[0196] Na2O is a component that improves moisture resistance and solubility. In addition, it also has the effect of suppressing the rise of the surface devitrification temperature and improving the average thermal expansion coefficient. Therefore, the glass of the first embodiment may contain Na2O. In the glass of the first embodiment, the solubility is improved by containing Na2O. In the glass of the first embodiment, the content of Na2O is more preferably 0.01% or more, more preferably 0.03% or more, more preferably 0.05% or more, more preferably 0.07% or more, particularly preferably 0.09% or more, and most preferably 0.1% or more.
[0197] In the glass of the first embodiment, from the viewpoint of dielectric properties, the content of Na2O is preferably 0.7% or less, more preferably 0.6% or less, further preferably 0.5% or less, further preferably 0.4% or less, further preferably 0.3% or less, and particularly preferably 0.2% or less.
[0198] Cl is a component that improves dielectric properties. In addition, it also acts as a clarifier and has the effect of reducing bubbles in the glass melt. In the glass of the first embodiment, it is preferred to contain 0.01 to 1% Cl. In the glass of the first embodiment, by containing 0.01% or more Cl, Abs-OH in the glass can be reduced, and with the reduction of Abs-OH, the relative dielectric constant and dielectric loss tangent can be reduced to improve the dielectric properties.
[0199] In the glass of the first embodiment, the Cl content is more preferably 0.01% or more, further preferably 0.02% or more, further preferably 0.03% or more, further preferably 0.04% or more, and particularly further preferably 0.05% or more. In addition, in the glass of the first embodiment, the Cl content is more preferably 1% or less, further preferably 0.9% or less, further preferably 0.8% or less, further preferably 0.7% or less, and particularly further preferably 0.6% or less.
[0200] In the glass of the first embodiment, the total content of SrO and BaO ([SrO] + [BaO]) is preferably 0.1 to 5.9%. In the glass of the first embodiment, by ([SrO] + [BaO]) being 0.1% or more, moisture resistance can be improved. In addition, it also has the effects of improving solubility, suppressing the increase in surface devitrification temperature, and improving the average thermal expansion coefficient. In the glass of the first embodiment, ([SrO] + [BaO]) is more preferably 0.1% or more, and the following are preferably: 0.2% or more, 0.3% or more, 0.4% or more, 0.5% or more, 0.6% or more, 0.7% or more, 0.8% or more, 0.9% or more, 1% or more, 1.1% or more, 1.2% or more, 1.3% or more, 1.4% or more, 1.5% or more, 1.6% or more, 1.7% or more, 1.8% or more, and 1.9% or more.
[0201] In the glass of the first embodiment, by ([SrO] + [BaO]) being 5.9% or less, deterioration of chemical resistance can be suppressed. In the glass of the first embodiment, ([SrO] + [BaO]) is more preferably 5.9% or less, and the following are preferably 5.8% or less, 5.7% or less, 5.6% or less, 5.5% or less, 5.4% or less, 5.3% or less, 5.2% or less, 5.1% or less, 5% or less, 4.9% or less, 4.8% or less, 4.7% or less, and 4.6% or less.
[0202] In the glass of the first embodiment, ([MgO] + [CaO]) - ([SrO] + [BaO]) is preferably -3 to 3%. In the glass of the first embodiment, when ([MgO] + [CaO]) - ([SrO] + [BaO]) is -3% or more, deterioration of chemical resistance can be suppressed. In the glass of the first embodiment, ([MgO] + [CaO]) - ([SrO] + [BaO]) is more preferably -3% or more, and the following are preferably: -2.9% or more, -2.8% or more, -2.7% or more, -2.6% or more, -2.5% or more, -2.4% or more, -2.3% or more, -2.2% or more, -2.1% or more, -2%, -1.9% or more, -1.8% or more, -1.7% or more, -1.6% or more, -1.5% or more, -1.4% or more, -1.3% or more, -1.2% or more, -1.1% or more, and -1% or more.
[0203] In the glass of the first embodiment, the moisture resistance can be improved by setting ([MgO] + [CaO]) - ([SrO] + [BaO]) to 3% or less. In the glass of the first embodiment, ([MgO] + [CaO]) - ([SrO] + [BaO]) is more preferably 3% or less, and the following are preferably 2.9% or less, 2.8% or less, 2.7% or less, 2.6% or less, 2.5% or less, 2.4% or less, 2.3% or less, 2.2% or less, 2.1% or less, and 2% or less.
[0204] [Glass of the Second Embodiment]
[0205] The glass of the second embodiment has the following structure in addition to the above-mentioned common structure, especially from the viewpoint of further improving solubility, chemical resistance, moisture resistance, phase separation characteristics and dielectric properties, and suppressing the increase of surface devitrification temperature.
[0206] Expressed as mol % based on oxide,
[0207] CaO is 0.1-6%,
[0208] The total content (RO) of MgO, CaO, SrO and BaO is greater than 0% and less than 6%, and the total content (R2O) of Li2O, Na2O and K2O is 0-1%.
[0209] [Al2O3]-[RO] is greater than -3% and less than 8%,
[0210] [Al2O3]×[RO] is greater than 0 and less than 28,
[0211] (([MgO]+[CaO])-([SrO]+[BaO])) / [Al2O3] is -3.0 to 0.60.
[0212] The glass of the second embodiment contains 0.1 to 6% of CaO. In the glass of the second embodiment, if the content of CaO is 0.1% or more, the average thermal expansion coefficient will not be too high, and the increase in the surface devitrification temperature can be suppressed. In the glass of the second embodiment, the content of CaO is preferably 0.15% or more, more preferably 0.2% or more, further preferably 0.25% or more, further preferably 0.3% or more, further preferably 0.35% or more, particularly further preferably 0.4% or more, further preferably 0.5% or more, further more preferably 0.6% or more, further more preferably 0.7% or more, further more preferably 0.8% or more, further more preferably 0.9% or more, and particularly further more preferably 1% or more.
[0213] In the glass of the second embodiment, if the content of CaO is 6% or less, the average thermal expansion coefficient will not be too high, and the increase in the surface devitrification temperature can be suppressed. In the glass of the second embodiment, the content of CaO is preferably 5.8% or less, more preferably 5.6% or less, further preferably 5.4% or less, further preferably 5.2% or less, further preferably 5% or less, particularly further preferably 4.8% or less, further preferably 4.6% or less, further more preferably 4.4% or less, further more preferably 4.2% or less, further more preferably 4% or less, further more preferably 3.8% or less, and particularly further more preferably 3.6% or less.
[0214] In the glass of the second embodiment, RO and R2O are the same as those of the glass of the first embodiment.
[0215] In the glass of the second embodiment, [Al 2 O 3 ]—[RO] is the same as that of the glass of the first embodiment.
[0216] In the glass of the second embodiment, [Al2O3]×[RO] is greater than 0 and is equal to or less than 28. In the glass of the second embodiment, the phase separation characteristics can be improved by [Al2O3]×[RO] being greater than 0. In the glass of the second embodiment, [Al2O3]×[RO] is preferably greater than 1, more preferably greater than 2, further preferably greater than 3, further preferably greater than 3.5, further preferably greater than 4, particularly further preferably greater than 4.5, further preferably greater than 5, further preferably greater than 5.5, further preferably greater than 6, further more preferably greater than 6.5, further more preferably greater than 7, and particularly further more preferably greater than 7.5.
[0217] In the glass of the second embodiment, when [Al2O3]×[RO] is 28 or less, the dielectric properties can be improved. In the glass of the second embodiment, [Al2O3]×[RO] is preferably 27 or less, more preferably 26 or less, further preferably 25 or less, further preferably 24 or less, still further preferably 23.5 or less, particularly further preferably 23 or less, still further preferably 22.5 or less, still further preferably 22 or less, further further preferably 21.5 or less, further further preferably 21 or less, further further preferably 20.5 or less, and particularly further preferably 20 or less.
[0218] In the glass of the second embodiment, (([MgO] + [CaO]) - ([SrO] + [BaO])) / [Al2O3] is -3.0 to 0.60. In the glass of the second embodiment, by making (([MgO] + [CaO]) - ([SrO] + [BaO])) / [Al2O3] -3.0 or more, chemical resistance can be improved.
[0219] In the glass of the second embodiment, (([MgO]+[CaO])-([SrO]+[BaO])) / [Al2O3] is preferably greater than -2.5, more preferably greater than -2.0, further preferably greater than -1.9, further preferably greater than -1.8, still further preferably greater than -1.7, particularly further preferably greater than -1.6, still more preferably greater than -1.5, still further preferably greater than -1.4, further more preferably greater than -1.3, further more preferably greater than -1.2, still further more preferably greater than -1.1, and particularly further more preferably greater than -1.0.
[0220] In the glass of the second embodiment, if (([MgO]+[CaO])-([SrO]+[BaO])) / [Al2O3] is 0.60 or less, moisture resistance can be improved. In the glass of the second embodiment, (([MgO]+[CaO])-([SrO]+[BaO])) / [Al2O3] is preferably 0.59 or less, more preferably 0.58 or less, further preferably 0.57 or less, particularly further preferably 0.56 or less, even more preferably 0.55 or less, still further preferably 0.54 or less, further more preferably 0.53 or less, further more preferably 0.52% or less, still further more preferably 0.51% or less, and particularly further more preferably 0.50% or less.
[0221] In the glass of the second embodiment, the total content of B2O3, MgO, BaO, Li2O, K2O, Na2O, Cl, SrO and BaO ([SrO]+[BaO]), ([MgO]+[CaO])-([SrO]+[BaO]) is the same as that of the glass of the first embodiment.
[0222] The glass of the second embodiment may contain SrO. In the glass of the second embodiment, by containing SrO, moisture resistance is improved and solubility is improved. In the glass of the second embodiment, when SrO is contained, the content is preferably 0.1% or more, more preferably 0.2% or more, further preferably 0.3% or more, further preferably 0.4% or more, further preferably 0.5% or more, and particularly preferably 0.6% or more.
[0223] In the glass of the second embodiment, from the viewpoint of suppressing the deterioration of chemical resistance, preventing the specific gravity from being too large, and suppressing an excessively high average thermal expansion coefficient, the SrO content is preferably 5.9% or less, more preferably 5.5% or less, further preferably 5% or less, further preferably 4.5% or less, further preferably 4% or less, and particularly preferably 3.5% or less.
[0224] [Glass of the third embodiment]
[0225] The glass of the third embodiment has the following structure in addition to the above-mentioned common structure, especially from the viewpoint of further improving solubility, moisture resistance, phase separation characteristics, dielectric properties, etc.
[0226] Expressed as mol % based on oxide,
[0227] Li2O is greater than 0%,
[0228] K2O is greater than 0% and less than 0.8%,
[0229] The total content of MgO, CaO, SrO and BaO (RO) is 0-0.5%,
[0230] The total content of Li2O, Na2O and K2O (R2O) is greater than 0% and less than 4%,
[0231] [Al2O3]×[R2O] is greater than 0 and less than 1.40,
[0232] [Na2O] / [R2O] is 0.30 to 0.99.
[0233] The glass of the third embodiment contains more than 0% Li2O. In the glass of the third embodiment, by containing more than 0% Li2O, the solubility and moisture resistance can be improved. In the glass of the third embodiment, the content of Li2O is preferably 0.1% or more, more preferably 0.2% or more, further preferably 0.3% or more, further preferably 0.4% or more, further preferably 0.5% or more, particularly further preferably 0.6% or more, more preferably 0.7% or more, further preferably 0.8% or more, further more preferably 0.9% or more, further more preferably 1.0% or more, further more preferably 1.1% or more, and particularly further more preferably 1.2% or more.
[0234] In the glass of the third embodiment, the content of Li2O is preferably 2.8% or less. In the glass of the third embodiment, if the content of Li2O is 2.8% or less, the deterioration of dielectric properties can be suppressed. In the glass of the third embodiment, the content of Li2O is more preferably 2.7% or less, further preferably 2.6% or less, further preferably 2.5% or less, further preferably 2.4% or less, particularly further preferably 2.3% or less, further preferably 2.2% or less, further more preferably 2.1% or less, further more preferably 2% or less, further more preferably 1.9% or less, further more preferably 1.8% or less, and particularly further more preferably 1.7% or less.
[0235] The glass of the third embodiment contains K2O in an amount greater than 0% and less than 0.8%. In the glass of the third embodiment, by having a K2O content greater than 0%, it is possible to improve solubility and moisture resistance. In the glass of the third embodiment, the K2O content is preferably greater than 0.02%, more preferably greater than 0.04%, further preferably greater than 0.06%, further preferably greater than 0.08%, particularly further preferably greater than 0.1%, further preferably greater than 0.12%, further more preferably greater than 0.14%, further more preferably greater than 0.16%, further more preferably greater than 0.18%, further more preferably greater than 0.20%, and particularly further more preferably greater than 0.22%.
[0236] In the glass of the third embodiment, if the content of K2O is 0.8% or less, deterioration of dielectric properties can be suppressed. In the glass of the third embodiment, the content of K2O is preferably 0.77% or less, more preferably 0.74% or less, further preferably 0.71% or less, further preferably 0.68% or less, further preferably 0.65% or less, particularly further preferably 0.62% or less, further preferably 0.59% or less, further more preferably 0.56% or less, further more preferably 0.53% or less, further more preferably 0.50% or less, further more preferably 0.47% or less, and particularly further more preferably 0.44% or less.
[0237] In the glass of the third embodiment, RO is 0 to 0.5%. The glass of the third embodiment may contain at least one selected from MgO, CaO, SrO and BaO. In the glass of the third embodiment, by containing at least one selected from MgO, CaO, SrO and BaO, moisture resistance can be improved. In the glass of the third embodiment, when containing at least one selected from MgO, CaO, SrO and BaO, RO is preferably 0.02% or more, more preferably 0.04% or more, further preferably 0.06% or more, and particularly preferably 0.08% or more.
[0238] In the glass of the third embodiment, by making RO 0.5% or less, it is possible to suppress the deterioration of the phase separation characteristics. In the glass of the third embodiment, RO is preferably 0.45% or less, more preferably 0.4% or less, further preferably 0.35% or less, further preferably 0.3% or less, further preferably 0.25% or less, and particularly preferably 0.2% or less.
[0239] In the glass of the third embodiment, R2O is greater than 0% and is 4% or less. In the glass of the third embodiment, R2O is greater than 0%, thereby improving solubility. In the glass of the third embodiment, R2O is preferably 0.1% or more, and the following are preferably: 0.2% or more, 0.3% or more, 0.4% or more, 0.5% or more, 0.6% or more, 0.7% or more, 0.8% or more, 0.9% or more, 1.0% or more, 1.1% or more, 1.2% or more, 1.3% or more, 1.4% or more, 1.5% or more, 1.6% or more, 1.7% or more, 1.8% or more, 1.9% or more, and 2.0% or more.
[0240] In the glass of the third embodiment, R2O is 4% or less, so that the dielectric properties can be suppressed from being deteriorated. In the glass of the third embodiment, R2O is preferably 3.9% or less, and the following are preferably 3.8% or less, 3.7% or less, 3.6% or less, 3.5% or less, 3.4% or less, 3.3% or less, 3.2% or less, 3.1% or less, 3.0% or less, 2.9% or less, 2.8% or less, 2.7% or less, 2.6% or less, and 2.5% or less.
[0241] In the glass of the third embodiment, [Al2O3]×[R2O] is greater than 0 and is less than or equal to 1.40. In the glass of the third embodiment, by [Al2O3]×[R2O] being greater than 0, the phase separation characteristics can be improved. In the glass of the third embodiment, [Al2O3]×[R2O] is preferably greater than or equal to 0.05, more preferably greater than or equal to 0.1, further preferably greater than or equal to 0.15, further preferably greater than or equal to 0.20, further preferably greater than or equal to 0.25, particularly further preferably greater than or equal to 0.30, further preferably greater than or equal to 0.35, further preferably greater than or equal to 0.40, further preferably greater than or equal to 0.45, further more preferably greater than or equal to 0.50, further more preferably greater than or equal to 0.55, and particularly further more preferably greater than or equal to 0.60.
[0242] In the glass of the third embodiment, if [Al2O3]×[R2O] is 1.40 or less, degradation of dielectric properties can be suppressed. In the glass of the third embodiment, [Al2O3]×[R2O] is preferably 1.40 or less, and the following are preferably 1.39 or less, 1.38 or less, 1.37 or less, 1.36 or less, 1.35 or less, 1.34 or less, 1.33 or less, 1.32 or less, 1.31 or less, 1.30 or less, 1.29 or less, 1.28 or less, 1.27 or less, 1.26 or less, 1.25 or less, 1.24 or less, 1.23 or less, Below 1.22, Below 1.21, Below 1.20, Below 1.19, Below 1.18, Below 1.17, Below 1.16, Below 1.15, Below 1.14, Below 1.13, Below 1.12, Below 1.11, Below 1.10, Below 1.09, Below 1.08, Below 1.07, Below 1.06, Below 1.05, Below 1.04, Below 1.03, Below 1.02, Below 1.01, Below 1.00.
[0243] In the glass of the third embodiment, [Na2O] / [R2O] is 0.30 to 0.99. In the glass of the third embodiment, the dielectric properties are improved by the alkali mixing effect due to the [Na2O] / [R2O] being 0.30 or more. In the glass of the third embodiment, [Na2O] / [R2O] is preferably 0.30 or more, more preferably 0.31 or more, further preferably 0.32 or more, further preferably 0.33 or more, further preferably 0.34 or more, particularly further preferably 0.35 or more, further preferably 0.36 or more, further preferably 0.37% or more, further preferably 0.38 or more, further more preferably 0.39 or more, further more preferably 0.40 or more, and particularly further more preferably 0.41 or more.
[0244] In the glass of the third embodiment, if [Na2O] / [R2O] is 0.99 or less, the dielectric properties are improved by the alkali mixing effect. In the glass of the third embodiment, [Na2O] / [R2O] is preferably 0.95 or less, more preferably 0.90 or less, further preferably 0.85 or less, further preferably 0.80 or less, further preferably 0.75 or less, particularly further preferably 0.70 or less, further preferably 0.68 or less, further more preferably 0.66 or less, further more preferably 0.64 or less, further more preferably 0.62 or less, further more preferably 0.60 or less, and particularly further more preferably 0.58 or less.
[0245] In the glass of the third embodiment, Cl is the same as that of the glass of the first embodiment.
[0246] The glass of the third embodiment preferably contains 18 to 29% of B2O3. In the glass of the third embodiment, by making the content of B2O3 18% or more, the solubility is improved. In addition, the dielectric loss tangent in the high frequency region can be reduced. The content of B2O3 is more preferably 18.5% or more, further preferably 19% or more, further preferably 19.5% or more, further preferably 20% or more, particularly preferably 20.5% or more, and most preferably 21% or more.
[0247] In the glass of the third embodiment, if B2O3 is 29% or less, chemical resistance can be improved. The content of B2O3 is more preferably 28% or less, further preferably 27% or less, further preferably 26% or less, further preferably 25% or less, and particularly preferably 24% or less.
[0248] The glass of the third embodiment may contain SrO. SrO is a component that has the effect of improving moisture resistance and suppressing the increase in devitrification temperature. In addition, it also has the effect of increasing the average thermal expansion coefficient. When the glass of the third embodiment contains SrO, it is preferably 0.01% or more, more preferably 0.02% or more, and further preferably 0.03% or more.
[0249] In the glass of the third embodiment, from the viewpoint of dielectric properties and chemical resistance, the SrO content is preferably 0.5% or less, and the following are preferably 0.45% or less, 0.4% or less, 0.3% or less, 0.2% or less, 0.1% or less, and 0.05% or less, respectively.
[0250] The glass of the third embodiment may contain CaO. CaO is a component that has the effect of improving solubility and suppressing the increase in devitrification temperature. When the glass of the third embodiment contains CaO, the content is preferably 0.01% or more, more preferably 0.02% or more, and further preferably 0.03% or more.
[0251] In the glass of the third embodiment, from the viewpoint of dielectric properties and phase separation properties, the CaO content is preferably 0.5% or less, and the following contents are preferably 0.45% or less, 0.4% or less, 0.3% or less, 0.2% or less, 0.1% or less, and 0.05% or less, respectively.
[0252] The glass of the third embodiment may contain MgO. MgO is a component that increases Young's modulus without increasing specific gravity. When MgO is contained in the glass of the third embodiment, the content is preferably 0.01% or more, more preferably 0.02% or more, and further preferably 0.03% or more.
[0253] In the glass of the third embodiment, from the viewpoint of dielectric properties and phase separation properties, the MgO content is preferably 0.5% or less, and the following preferred contents are: 0.45% or less, 0.4% or less, 0.3% or less, 0.2% or less, 0.1% or less, and 0.05% or less, respectively.
[0254] The glass of the third embodiment may contain BaO. BaO is a component that has the effect of improving moisture resistance and suppressing the increase in devitrification temperature. In addition, it also has the effect of increasing the average thermal expansion coefficient. When the glass of the third embodiment contains BaO, it is preferably 0.01% or more, more preferably 0.02% or more, and further preferably 0.03% or more.
[0255] In the glass of the third embodiment, from the viewpoint of dielectric properties and chemical resistance, the BaO content is preferably 0.5% or less, and the following preferred contents are: 0.45% or less, 0.4% or less, 0.3% or less, 0.2% or less, 0.1% or less, and 0.05% or less, in that order.
[0256] In the glass of the third embodiment, Na2O is a component having the effect of improving solubility and moisture resistance. In the glass of the third embodiment, it is preferred that Na2O be contained in an amount greater than 0 and less than 3.9%. By making the content of Na2O greater than 0%, solubility is improved. The content of Na2O is more preferably greater than 0.1%, and the following are preferably in order: greater than 0.2%, greater than 0.3%, greater than 0.4%, greater than 0.5%, greater than 0.6%, greater than 0.7%, greater than 0.8%, greater than 0.9%, greater than 1%, greater than 1.1%, and greater than 1.2%.
[0257] In the glass of the third embodiment, from the viewpoint of dielectric properties, the content of Na2O is preferably 3.9% or less. The content of Na2O is more preferably 3.8% or less, and the following are preferably 3.7% or less, 3.6% or less, 3.5% or less, 3.4% or less, 3.3% or less, 3.2% or less, 3.1% or less, 3.0% or less, 2.9% or less, 2.8% or less, 2.7% or less, 2.6% or less, 2.5% or less, 2.4% or less, 2.3% or less, 2.2% or less, 2.1% or less, 2.0%, 1.9% or less, 1.8% or less, and 1.7% or less.
[0258] In the glass of the third embodiment, [Al2O3]×[RO] is preferably 0 to 0.4. From the viewpoint of dielectric properties, [Al2O3]×[RO] is more preferably 0.35 or less, and the following are preferably 0.30 or less, 0.25 or less, 0.20 or less, 0.15 or less, and 0.10 or less, respectively.
[0259] In the glass of the third embodiment, the total content of MgO and CaO ([MgO] + [CaO]) is preferably 0 to 0.5%. In the glass of the third embodiment, if [MgO] + [CaO] is 0.5% or less, the deterioration of dielectric properties can be suppressed. In the glass of the third embodiment, [MgO] + [CaO] is more preferably 0.45% or less, and the following are preferably: 0.40% or less, 0.35% or less, 0.30% or less, 0.25% or less, 0.20% or less, 0.15% or less, 0.10% or less, and 0.05% or less.
[0260] In the glass of the third embodiment, the lower limit of [MgO]+[CaO] may be 0%. When it is not 0%, it is more preferably 0.001% or more, further preferably 0.005% or more, and further preferably 0.01% or more.
[0261] In the glass of the third embodiment, the total content of SrO and BaO ([SrO] + [BaO]) is preferably 0 to 0.5%. By setting ([SrO] + [BaO]) to 0.5% or less, it is possible to suppress the degradation of dielectric properties. In the glass of the third embodiment, ([SrO] + [BaO]) is more preferably 0.45% or less, and the following are preferably: 0.40% or less, 0.35% or less, 0.30% or less, 0.25% or less, 0.20% or less, 0.15% or less, 0.10% or less, and 0.05% or less.
[0262] In the glass of the third embodiment, the lower limit of [SrO]+[BaO] may be 0%. When it is not 0%, it is more preferably 0.001% or more, further preferably 0.005% or more, and further preferably 0.01% or more.
[0263] In the glass of the third embodiment, ([MgO] + [CaO]) - ([SrO] + [BaO]) is preferably -0.5 to 0.5%. In the glass of the third embodiment, by ([MgO] + [CaO]) - ([SrO] + [BaO]) being -0.5% or more, it is possible to suppress deterioration in chemical resistance. In the glass of the third embodiment, ([MgO] + [CaO]) - ([SrO] + [BaO]) is more preferably -0.4% or more, and the following are preferably -0.3% or more, -0.2% or more, and -0.1% or more, respectively.
[0264] In the glass of the third embodiment, the moisture resistance can be improved by setting ([MgO]+[CaO])-([SrO]+[BaO]) to 0.5% or less. In the glass of the first embodiment, ([MgO]+[CaO])-([SrO]+[BaO]) is more preferably 0.4% or less, and the following are preferably 0.3% or less, 0.2% or less, and 0.1% or less, respectively.
[0265] In the glass of the third embodiment, [MgO] / ([MgO]+[Al2O3]) is preferably 0 to 0.45. In the glass of the third embodiment, by [MgO] / ([MgO]+[Al2O3]) being 0.45 or less, the rise in the surface devitrification temperature can be suppressed. In the glass of the first embodiment, [MgO] / ([MgO]+[Al2O3]) is more preferably 0.44 or less, further preferably 0.43 or less, further preferably 0.42 or less, further preferably 0.41 or less, particularly further preferably 0.4 or less, further preferably 0.39 or less, further preferably 0.35 or less, further preferably 0.31 or less, further more preferably 0.3 or less, further more preferably 0.25 or less, and particularly further more preferably 0.2 or less.
[0266] In the glass of the third embodiment, [MgO] / ([MgO]+[Al2O3]) may be 0. When it is not 0, it is more preferably 0.001 or more, further preferably 0.005 or more, and particularly further preferably 0.01 or more.
[0267] Hereinafter, other components and properties in the glass of the present invention including the first to third embodiments will be described.
[0268] 〔Other ingredients and properties〕
[0269] In order to improve the clarity of the glass, the glass of the present invention may contain SO3. When the glass of the present invention contains SO3, the content of SO3 is preferably 0.0001% or more, more preferably 0.0005% or more, and further preferably 0.001% or more, expressed as a mass percentage based on the oxide. In addition, the content of SO3 is preferably 1% or less, more preferably 0.5% or less, and further preferably 0.1% or less.
[0270] In order to improve the solubility of the glass, the glass of the present invention may contain Fe. However, from the viewpoint of reducing the coloring of the glass, the transmittance in the visible region, and reducing the relative dielectric constant and dielectric loss tangent in the high-frequency region, the Fe content is preferably 0.15% or less, more preferably 0.1% or less, further preferably 0.05% or less, and further preferably 0.03% or less, expressed as a mass percentage of an oxide basis calculated as Fe2O3. In addition, when the glass of the present invention contains Fe, the Fe content is preferably 0.0001% or more, more preferably 0.0005% or more, and further preferably 0.001% or more.
[0271] The glass of the present invention preferably has an Abs-OH of 0.1 to 10. Abs-OH is an indicator of the water content in the glass. After both surfaces of a glass sample are mirror-polished to form a glass plate with a thickness of 0.45 to 0.75 mm, the Abs-OH is measured using FT-IR at a wave number of 4000 to 2000 cm -1 The transmittance was measured within the range of 3846 cm. -1 The transmittance at τ1 (%) is set, and the absorption band from hydroxyl group, i.e., the wave number 3700-3200 cm -1 The minimum value of the transmittance at is defined as τ2(%), and Abs-OH is calculated by the following formula.
[0272] Abs-OH=log 10 (τ2 / 100) / log 10 (τ1 / 100)
[0273] When Abs-OH is 0.1 or more, the glass viscosity is 10 2 dPa·s, the resistance value at temperature T2 becomes lower, which is suitable for melting the glass by electric heating, and there are fewer bubble defects in the glass. Therefore, if Abs-OH is 0.1 or more, the solubility is improved. If Abs-OH is 10 or less, the bubble defects in the glass can be suppressed. Abs-OH is more preferably 9.0 or less, more preferably 8.0 or less, and more preferably 7.0 or less. Abs-OH is more preferably 0.5 or more, more preferably 1.0 or more, more preferably 1.5 or more, more preferably 2.0 or more, and particularly preferably 2.5 or more.
[0274] The wave number 3846cm is the standard for being less susceptible -1 The index of the water content of the glass affected by the transmittance τ1(%) at Base =-log 10 (τ1 / 100), Abs β-OH =-log 10(τ2 / 100), we can also cite (Abs β-OH -Abs Base ). In the glass of the present invention, (Abs β-OH -Abs Base ) is preferably greater than 0.02.
[0275] If (Abs β-OH -Abs Base ) is 0.02 or more, the glass viscosity is 10 2 dPa·s The resistance value at temperature T2 becomes lower, which is suitable for melting the glass by electric heating, and there are fewer bubble defects in the glass. Therefore, if (Abs β-OH -Abs Base ) is 0.02 or more, since the solubility is improved, so it is preferred. β-OH -Abs Base ) is 0.5 or less, the bubble defects in the glass can be suppressed. (Abs β-OH -Abs Base ) is more preferably 0.4 or less, further preferably 0.35 or less, further preferably 0.3 or less, and particularly preferably 0.25 or less. (Abs β-OH -Abs Base ) is more preferably greater than 0.03, further preferably greater than 0.05, further preferably greater than 0.1, still further preferably greater than 0.125, particularly preferably greater than 0.15, and particularly preferably greater than 0.175.
[0276] In order to improve the clarity of the glass, the glass of the present invention may contain SnO2. The content of SO3 is preferably 0.001% or more, more preferably 0.01% or more, and further preferably 0.1% or more. In addition, from the viewpoint of dielectric properties, the content of SnO2 in the glass of the present invention is preferably 1% or less, more preferably 0.5% or less, and further preferably 0.2% or less.
[0277] In order to improve the chemical resistance of the glass, the glass of the present invention may contain at least one selected from Sc2O3, TiO2, ZnO, Ga2O3, GeO2, Y2O3, ZrO2, Nb2O5, In2O3, TeO2, HfO2, Ta2O5, WO3, Bi2O3, La2O3, Gd2O3, Yb2O3 and Lu2O3 as a trace component. If the content of the trace components is too large, the phase separation characteristics of the glass are likely to decrease, so the total content of the trace components is preferably 1% or less, more preferably 0.25% or less, further preferably 0.2% or less, further preferably 0.1% or less, and further preferably 0.05% or less.
[0278] The glass of the present invention may contain only one of the above-mentioned trace components, or may contain two or more of them.
[0279] The glass of the present invention may contain P2O5 in order to improve the solubility of the glass, etc. The content of P2O5 is preferably 2% or less, more preferably 1% or less, further preferably 0.5% or less, further preferably 0.3% or less, and further preferably 0.1% or less.
[0280] On the other hand, since P2O5 may evaporate in the glass forming equipment and then condense and fall onto the glass plate, becoming a foreign matter defect, it is particularly preferred that the content is 0.05% or less, more preferably 0.01% or less, and even more preferably 0.005% or less, and most preferably substantially free of P2O5. In the present invention, substantially free of P2O5 means that it does not contain any impurities other than those inevitably mixed in from the raw materials, that is, it is not intentionally contained.
[0281] To improve the solubility of glass, reduce the strain point of glass, and reduce T g The glass of the present invention may contain F for the purpose of reducing the slow cooling point, reducing the dielectric loss tangent, etc. The F content is preferably 0.1 mol% or more, more preferably 0.2 mol% or more, and further preferably 0.4 mol% or more. Among them, from the viewpoint of suppressing the quality reduction of the glass caused by the volatilization of F, the F content is preferably 1.5 mol% or less, more preferably 1 mol% or less, further preferably 0.5 mol% or less, and further preferably 0.1 mol% or less.
[0282] The F content is preferably 0.01% or more, more preferably 0.03% or more, expressed as a mass percentage, and the upper limit is preferably 0.2% or less, more preferably 0.1% or less, and further preferably 0.05% or less.
[0283] The glass of the present invention may contain at least one selected from Se2O3, TeO2, Ga2O3, In2O3, GeO2, CdO, BeO and Bi2O3 in order to improve the solubility, clarity, formability and the like of the glass, to obtain absorption at a specific wavelength, and to improve density, hardness, bending rigidity, durability and the like. The total content of these is preferably 2% or less, more preferably 1% or less, further preferably 0.5% or less, further preferably 0.3% or less, still further preferably 0.1% or less, particularly further preferably 0.05% or less, and even more preferably 0.01% or less.
[0284] The glass of the present invention may contain a rare earth oxide or a transition metal oxide in order to improve the solubility, clarity, formability, etc. of the glass and in order to improve the hardness of the glass, for example, Young's modulus, etc.
[0285] The glass of the present invention may contain at least one selected from the group consisting of Sc2O3, Y2O3, La2O3, Ce2O3, Pr2O3, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb2O3, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3 and Lu2O3 as a rare earth oxide. The total content of these is preferably 2% or less, more preferably 1% or less, further preferably 0.5% or less, further preferably 0.3% or less, further preferably 0.1% or less, particularly preferably 0.05% or less, and even more preferably 0.01% or less.
[0286] The glass of the present invention may contain at least one selected from V2O5, Ta2O3, Nb2O5, WO3, MoO3 and HfO2 as a transition metal oxide. The total content of these oxides is preferably 2% or less, more preferably 1% or less, further preferably 0.5% or less, further preferably 0.3% or less, further preferably 0.1% or less, further preferably 0.05% or less, and further preferably 0.01% or less.
[0287] The glass of the present invention may contain ThO2 as an actinide oxide in order to improve the solubility of the glass, etc. The content of ThO2 is preferably 2% or less, more preferably 1% or less, further preferably 0.5% or less, further preferably 0.3% or less, further preferably 0.1% or less, particularly further preferably 0.05% or less, further preferably 0.01% or less, and further preferably 0.005% or less.
[0288] The dielectric loss tangent of the glass of the present invention at 20°C and a frequency of 35 GHz is preferably 0.005 or less. If the dielectric loss tangent at 20°C and a frequency of 35 GHz is 0.005 or less, the dielectric loss in the high frequency region exceeding 30 GHz can be reduced. The dielectric loss tangent at 20°C and a frequency of 35 GHz is preferably 0.0045 or less, more preferably 0.0040 or less, further preferably 0.0035 or less, further preferably 0.0030 or less, and further preferably 0.0025 or less. The lower limit is not particularly limited, for example, preferably 0.0001 or more.
[0289] The relative dielectric constant of the glass of the present invention at 20° C. and 35 GHz is preferably 4.5 or less, more preferably 4.45 or less, further preferably 4.4 or less, further preferably 4.35 or less, and further preferably 4.3 or less. The lower limit is not particularly limited, but is preferably 3 or more, for example.
[0290] The density of the glass of the present invention is preferably 2.58 g / cm 3As a result, the self-weight deflection is reduced, and the handling of large substrates becomes easier. In addition, the weight of equipment using glass can be reduced. The density is more preferably 2.5g / cm 3 Below, more preferably 2.4 g / cm 3 Below, further preferably 2.35 g / cm 3 Below, more preferably 2.3 g / cm 3 The lower limit is not particularly limited, but is preferably 2 g / cm 3 above.
[0291] In addition, a large-scale substrate refers to a substrate having at least one side of 1000 mm or more, for example.
[0292] The glass viscosity of the glass of the present invention is 10 2 The temperature T2 of dPa·s (hereinafter referred to as temperature T2) is preferably below 1950°C. If the temperature T2 is below 1950°C, the solubility of the glass is excellent, and the burden on the manufacturing equipment can be reduced. For example, the life of equipment such as a kiln for melting glass can be extended, and productivity can be improved. In addition, defects from the kiln, such as pitting defects and Zr defects, can be reduced. T2 is more preferably below 1940°C, further preferably below 1930°C, further preferably below 1900°C, further preferably below 1880°C, and particularly preferably below 1850°C.
[0293] The lower limit of the temperature T2 is not particularly limited, but is preferably 1500° C. or higher, for example. In order to use SO 3 as a clarifier, the lower limit is preferably 1600° C. or higher, and more preferably 1650° C. or higher.
[0294] The glass of the present invention has a temperature of 10 4 The temperature T4 of dPa·s (hereinafter referred to as temperature T4) is preferably 1450°C or less. If the temperature T4 is 1450°C or less, the moldability of the glass is excellent. In addition, for example, by lowering the temperature during glass molding, the volatiles in the atmosphere around the glass can be reduced, thereby reducing the shortcomings of the glass. Since the glass can be molded at a low temperature, the burden on the manufacturing equipment can be reduced. For example, the life of equipment such as a float bath for molding the glass can be extended, and productivity can be improved. The temperature T4 is more preferably 1440°C or less, further preferably 1430°C or less, particularly preferably 1420°C or less, further preferably 1400°C or less, further preferably 1380°C or less, and particularly preferably 1350°C or less.
[0295] The lower limit of the temperature T4 is not particularly limited, but is preferably 1050° C. or higher, for example.
[0296] Temperatures T2 and T4 are obtained by measuring the viscosity using a rotational viscometer according to the method specified in ASTM C 965-96 (2017) to obtain a viscosity of 10 2 dPa·s or 10 4 dPa·s at a temperature. In the examples described below, NBS710 and NIST SRM717a were used as reference samples for calibration of the device.
[0297] The glass transition temperature T of the glass of the present invention is g It is preferably below 750°C. g If the temperature is 750°C or lower, it is possible to avoid the need to increase the temperature of the slow cooling device, thereby suppressing the reduction in the life of the slow cooling device. g The temperature is more preferably 730°C or lower, and even more preferably 700°C or lower.
[0298] Temperature T g The lower limit of the temperature is not particularly limited, but is preferably 450° C. or higher, for example.
[0299] The annealing point of the glass of the present invention is preferably 750° C. or lower. If the annealing point is 750° C. or lower, the need to increase the temperature of the annealing device can be avoided, and the reduction in the life of the annealing device can be suppressed. The annealing point is more preferably 730° C. or lower, and further preferably 700° C. or lower.
[0300] The lower limit of the slow cooling point is not particularly limited, but is preferably 450° C. or higher, for example.
[0301] The surface devitrification temperature of the glass of the present invention is preferably below 1400°C. If the surface devitrification temperature is below 1400°C, the glass has excellent formability. It is possible to suppress the generation of crystals inside the glass during molding, thereby reducing transmittance. In addition, it is possible to reduce the burden on manufacturing equipment. For example, it is possible to extend the life of equipment such as a float bath for molding the glass, thereby improving productivity.
[0302] The surface devitrification temperature is more preferably 1390° C. or less, further preferably 1380° C. or less, further preferably 1370° C. or less, still further preferably 1360° C. or less, particularly further preferably 1355° C. or less, and still more preferably 1350° C. or less. The lower limit of the surface devitrification temperature is not particularly limited, and is, for example, preferably 900° C. or more.
[0303] The surface devitrification temperature in the present invention is obtained as follows. That is, crushed glass particles are loaded into a platinum dish, and heat-treated for 17 hours in an electric furnace controlled to a constant temperature. After the heat treatment, an optical microscope is used to observe the maximum temperature at which crystals are precipitated on the surface of the glass and the minimum temperature at which crystals are not precipitated, and its average value is used as the surface devitrification temperature.
[0304] The average thermal expansion coefficient of the glass of the present invention at 50 to 350°C is preferably 20×10 -7 / K or more. If the average thermal expansion coefficient at 50-350°C is 20×10 -7 / K or more, when the glass substrate is made, it is possible to prevent the expansion coefficient difference with the metal film formed on the glass substrate from being too large and causing cracking. The average thermal expansion coefficient at 50 to 350°C is more preferably 25×10 -7 / K or above.
[0305] On the other hand, the average thermal expansion coefficient at 50 to 350°C is preferably 50×10 -7 / K or less. If the average thermal expansion coefficient at 50-350°C is 50×10 -7 / K or less, the glass can be prevented from cracking during the manufacturing process of products such as high-frequency devices. The average thermal expansion coefficient at 50 to 350°C is more preferably 40×10 -7 / K or less, more preferably 37×10 -7 / K or less, and more preferably 35×10 -7 / K or less.
[0306] When the glass of the present invention is immersed in an aqueous solution containing 7.7 mass % HNO3 and 6.5 mass % H2SO4 at 45°C for 170 seconds, the amount of glass component dissolved per unit surface area is preferably 0.05 mg / cm 2 When the above test is performed, the shape and size of the glass is a plate-like sample with a side of 31 to 36 mm and a thickness of 0.45 to 0.75 mm. The weight before immersion is expressed as weight Before , the weight after immersion is expressed as weight After When the vertical and horizontal lengths of the plate-like sample before immersion are expressed as length and width respectively, and the thickness is expressed as thickness, the elution amount of the glass component per unit surface area is calculated by the following formula.
[0307]
[0308] When the amount of the glass component dissolved is within the above range, the acid resistance is good. The amount of the glass component dissolved is more preferably 0.04 mg / cm 2 Below, more preferably 0.03 mg / cm 2 Below, particularly preferably 0.02 mg / cm 2 the following.
[0309] The lower limit of the amount of glass component dissolved is not particularly limited, but is preferably 0.0001 mg / cm 2 above.
[0310] When the glass of the present invention is immersed in an aqueous solution containing 1.2 mass % KOH at 60° C. for 30 minutes, the amount of glass component eluted per unit surface area is preferably 0.15 mg / cm 2 When the above test is performed, the shape and size of the glass is a plate-like sample with a side of 31 to 36 mm and a thickness of 0.45 to 0.75 mm. The weight before immersion is expressed as weight Before , the weight after immersion is expressed as weight After When the vertical and horizontal lengths of the plate-like sample before immersion are expressed as length and width respectively, and the thickness is expressed as thickness, the elution amount of the glass component per unit surface area is calculated by the following formula.
[0311]
[0312] When the amount of the glass component dissolved is within the above range, the alkali resistance is good. The amount of the glass component dissolved is more preferably 0.12 mg / cm 2 Below, more preferably 0.10 mg / cm 2 Below, particularly preferably 0.80 mg / cm 2 the following.
[0313] The lower limit of the amount of glass component dissolved is not particularly limited, but is preferably 0.0001 mg / cm 2 above.
[0314] The Young's modulus of the glass of the present invention is preferably 40 GPa or more. If the Young's modulus is within the above range, it is possible to suppress the occurrence of undesirable conditions such as warping, bending, and cracking of the glass substrate after the formation of a metal film, such as a Cu film, in the manufacturing process of a high-frequency device. The Young's modulus is more preferably 43 GPa or more, further preferably 45 GPa or more, and further preferably 47 GPa or more.
[0315] The upper limit of the Young's modulus is not particularly limited, but is preferably 70 GPa or less, for example.
[0316] The specific elastic modulus of the glass of the present invention is preferably 20 MN·m / kg or more. If the specific elastic modulus is within the above range, the deflection of the glass can be suppressed. The specific elastic modulus is more preferably 21 MN·m / kg or more, and further preferably 22 MN·m / kg or more.
[0317] The upper limit of the specific elastic modulus is not particularly limited, but is, for example, preferably 35 MN·m / kg or less, more preferably 30 MN·m / kg or less, and further preferably 25 MN·m / kg or less.
[0318] 〔glass plate〕
[0319] The glass plate including the glass of the present invention (hereinafter referred to as the glass plate of the present invention) is suitable for glass substrates for high-frequency devices, panel-type antennas, window glass, vehicle window glass, cover glass for touch panels, and the like due to the above-mentioned characteristics.
[0320] Figure 1 This is a cross-sectional view showing an example of the structure of a circuit board for a high-frequency device. Figure 1 The circuit substrate 1 shown in the figure comprises: a glass substrate 2 having insulating properties, a first wiring layer 3 formed on a first main surface 2a of the glass substrate 2, and a second wiring layer 4 formed on a second main surface 2b of the glass substrate 2. The first and second wiring layers 3 and 4 form a microstrip line as an example of a transmission line. The first wiring layer 3 constitutes a signal wiring, and the second wiring layer 4 constitutes a ground line. However, the structure of the first and second wiring layers 3 and 4 is not limited to this. In addition, the wiring layer may be formed only on one main surface of the glass substrate 2.
[0321] The first and second wiring layers 3 and 4 are layers formed of conductors, and their thickness is usually about 0.1 to 50 μm. The conductors forming the first and second wiring layers 3 and 4 are not particularly limited. For example, metals such as copper, gold, silver, aluminum, titanium, chromium, molybdenum, tungsten, platinum, and nickel, alloys containing at least one of these metals, and metal compounds can be used. The structure of the first and second wiring layers 3 and 4 is not limited to a single-layer structure. For example, they can have a multilayer structure such as a stacked structure of a titanium layer and a copper layer. The method for forming the first and second wiring layers 3 and 4 is not particularly limited. For example, various known formation methods such as printing method, dipping method, plating method, evaporation method, and sputtering using a conductor paste can be applied.
[0322] When the glass plate of the present invention is used as the glass substrate 2, the dielectric loss tangent of the glass substrate 2 at a frequency of 10 GHz is preferably 0.005 or less. If the dielectric loss tangent of the glass substrate 2 at a frequency of 10 GHz is 0.005 or less, the dielectric loss in the high frequency region exceeding 10 GHz can be reduced. The dielectric loss tangent of the glass substrate 2 at a frequency of 10 GHz is more preferably 0.0045 or less, further preferably 0.0040 or less, further preferably 0.0035 or less, further preferably 0.0030 or less, and particularly preferably 0.0025 or less.
[0323] If the relative dielectric constant of the glass substrate 2 at a frequency of 10 GHz is 4.5 or less, the dielectric loss in the high frequency region can be reduced, so it is preferred. The relative dielectric constant of the glass substrate 2 at a frequency of 10 GHz is more preferably 4.45 or less, further preferably 4.40 or less, further preferably 4.35 or less, further preferably 4.30 or less, particularly further preferably 4.25 or less, further preferably 4.20 or less, further more preferably 4.15 or less, and further more preferably 4.10 or less.
[0324] Furthermore, the glass substrate 2 has main surfaces 2a, 2b and end surfaces. For at least one of the main surfaces 2a, 2b of the glass substrate 2 forming the first and second wiring layers 3, 4, the arithmetic mean roughness Ra is preferably 1.5 nm or less as the surface roughness, and the arithmetic mean roughness Ra of the two main surfaces is more preferably 1.5 nm or less. If the arithmetic mean roughness Ra of the main surface is within the above range, even in the high frequency region exceeding 30 GHz, when the skin effect occurs in the first and second wiring layers 3, 4, the surface resistance of the first and second wiring layers 3, 4 can be reduced, thereby reducing the conductor loss.
[0325] The arithmetic mean roughness Ra of the main surfaces 2a and 2b of the glass substrate 2 is more preferably 1 nm or less, and more preferably 0.5 nm or less. The main surface of the glass substrate 2 refers to the surface on which the wiring layer is formed. When the wiring layer is formed on one main surface, it is sufficient to make the value of the arithmetic mean roughness Ra of one main surface satisfy 1.5 nm or less. It should be noted that the arithmetic mean roughness Ra in this specification refers to the value based on JIS B0601 (2001).
[0326] The surface roughness of the main surfaces 2a and 2b of the glass substrate 2 can be achieved by grinding the surface of the glass substrate 2 as required. The grinding of the surface of the glass substrate 2 can be applied, for example, by grinding using a grinding agent and a grinding pad mainly composed of cerium oxide, colloidal silica, etc.; grinding using a grinding slurry and a grinding pad containing a grinding agent and an acidic or alkaline dispersion medium; grinding using an acidic or alkaline etching solution, etc.
[0327] The above-mentioned grinding treatment can be applied according to the surface roughness of the blank plate of the glass substrate 2. For example, pre-grinding and finish grinding can be used in combination. In addition, in order to prevent the glass substrate 2 from being broken, cracked, or damaged due to the end face during the process, the end face of the glass substrate 2 is preferably chamfered. The chamfering can be any of C chamfering, R chamfering, and slight chamfering.
[0328] By using such a glass substrate 2, the transmission loss of the circuit substrate 1 at a frequency of 10 GHz can be reduced. For example, it can be reduced to less than 1 dB / cm. Therefore, the quality or strength of high-frequency signals, especially high-frequency signals above 10 GHz, can be maintained, so that a glass substrate 2 and a circuit substrate 1 suitable for high-frequency devices that process such high-frequency signals can be provided. That is, the characteristics and quality of high-frequency devices that process such high-frequency signals can be improved. The transmission loss of the circuit substrate 1 at a frequency of 10 GHz is preferably less than 1 dB / cm.
[0329] The shape of the glass plate of the present invention is not particularly limited, and the thickness is preferably 0.75 mm or less. If the thickness of the glass plate is 0.75 mm or less, when used as a glass substrate for high-frequency devices, the high-frequency devices can be thinned and miniaturized, thereby improving production efficiency. In addition, the ultraviolet transmittance is improved, and ultraviolet curing materials can be used in the manufacturing process of the equipment to improve manufacturability. The thickness of the glass plate is more preferably 0.7 mm or less, more preferably 0.6 mm or less, more preferably 0.5 mm or less, more preferably 0.4 mm or less, and more preferably 0.3 mm or less. In addition, the thickness of the glass plate is preferably 0.01 mm or more, more preferably 0.05 mm or more, and more preferably 0.1 mm or more.
[0330] When the glass plate is made into a large substrate, at least one side is preferably 1000 mm or more, more preferably 1500 mm or more, and further preferably 1800 mm or more. The upper limit is not particularly limited, and the size of one side is usually 4000 mm or less. In addition, the glass plate is preferably rectangular.
[0331] [Method for manufacturing glass plate]
[0332] Next, the manufacturing method of the glass plate of the present invention is described. When manufacturing a glass plate, the following steps are performed: a melting step of heating glass raw materials to obtain molten glass; a clarification step of removing bubbles from the molten glass; a forming step of forming the molten glass into a plate to obtain a glass ribbon; and a slow cooling step of slowly cooling the glass ribbon to room temperature. Alternatively, a method of forming the molten glass into a block, slowly cooling it, and then cutting and grinding it to manufacture a glass plate may be used.
[0333] In the melting process, raw materials are prepared in a manner to obtain a target glass composition, and the raw materials are continuously put into a melting furnace and heated to preferably about 1450 to 1750° C. to obtain molten glass. The glass of this embodiment has a low resistance value in the temperature range for melting the glass raw materials, for example, around 1500° C., so it is preferred to use an electric melting furnace as the melting furnace and melt the glass by electric heating. However, electric heating and heating using a burner may be used in combination.
[0334] Raw materials may also be halides such as oxides, carbonates, nitrates, hydroxides, and chlorides. When there is a step in which molten glass contacts platinum during the melting and clarification steps, sometimes tiny platinum particles are dissolved into the molten glass and mixed into the obtained glass plate as foreign matter, but the use of nitrate raw materials has the effect of preventing the formation of platinum foreign matter.
[0335] As nitrates, strontium nitrate, barium nitrate, magnesium nitrate, calcium nitrate, etc. can be used. Strontium nitrate is more preferably used. Regarding the particle size of the raw materials, raw materials with large particle sizes of several hundred μm that will not produce molten residues, and raw materials with small particle sizes of several μm that will not cause the raw materials to fly around during transportation and will not agglomerate into secondary particles, can all be used appropriately. Granulated bodies can also be used. In order to prevent the raw materials from flying around, the water content of the raw materials can also be appropriately adjusted. The redox degree of Abs-OH and Fe (redox [Fe 2+ / (Fe 2+ +Fe 3+ )])'s melting conditions.
[0336] The next clarification step is a step of removing bubbles from the molten glass obtained in the above-mentioned melting step. As a clarification step, a degassing method based on reduced pressure can be applied, or degassing can be performed by making the temperature higher than the melting temperature of the raw materials. In addition, SO3 and SnO2 can be used as clarifiers. As a SO3 source, it is preferred to select at least one sulfate of an element selected from Al, Na, K, Mg, Ca, Sr and Ba, and more preferably an alkaline earth metal sulfate, among which CaSO4·2H2O, SrSO4 and BaSO4 have a significant effect on increasing bubbles and are particularly preferred.
[0337] As a clarifier in the degassing method based on reduced pressure, halogens such as Cl or F are preferably used. As a Cl source, a chloride of at least one element selected from Al, Mg, Ca, Sr and Ba is preferred, and a chloride of an alkaline earth metal is more preferred. Among them, SrCl2·6H2O and BaCl2·2H2O have a significant effect of increasing bubbles and low deliquescent properties, so they are more preferred. As a F source, a fluoride of at least one element selected from Al, Na, K, Mg, Ca, Sr and Ba is preferred, and a fluoride of an alkaline earth metal is more preferred. Among them, CaF2 has a significant effect of increasing the solubility of glass raw materials, so it is more preferred.
[0338] Tin compounds represented by SnO2 generate O2 gas in glass melt. In glass melt, SnO2 is reduced to SnO at a temperature above 1450°C, generating O2 gas, which has the effect of greatly increasing the size of bubbles. When manufacturing glass sheets, the glass raw materials are heated to about 1450-1750°C to melt them, so the bubbles in the glass melt are more effectively enlarged.
[0339] When SnO2 is used as a clarifier, it is preferred to prepare the raw material in such a way that 0.001% or more of tin compounds are contained in terms of SnO2 relative to 100% of the total amount of the mother composition. If the SnO2 content is 0.001% or more, a clarification effect can be obtained during the melting of the glass raw material, so it is preferred. The SnO2 content is more preferably 0.015% or more, and further preferably 0.1% or more. If the SnO2 content is 1% or less, the coloring and devitrification of the glass can be suppressed, so it is preferred. The content of tin compounds in the glass is more preferably 0.5% or less in terms of SnO2 relative to 100% of the total amount of the glass mother composition, and further preferably 0.2% or less.
[0340] The next forming step is a step of forming the molten glass from which bubbles have been removed in the above-mentioned clarification step into a plate shape to obtain a glass ribbon. As the forming step, the following methods can be applied: a float method in which molten glass is flowed onto a molten metal such as tin to form a plate shape to obtain a glass ribbon, an overflow down-draw method (melting method) in which molten glass flows downward from a gutter-shaped member, a slit down-draw method in which molten glass flows from a slit, and other well-known methods of forming glass into a plate shape. Among them, the float method or the melting method is preferred from the viewpoint of no grinding and light grinding.
[0341] Next, the slow cooling step is a step of cooling the glass ribbon obtained in the above-mentioned forming step under cooling conditions controlled to room temperature. In the slow cooling step, the glass ribbon is cooled to form a glass ribbon, and then slowly cooled to room temperature under predetermined conditions. The slowly cooled glass ribbon is cut to obtain a glass sheet.
[0342] If the cooling rate in the slow cooling process is too fast, it is easy to leave residual strain in the cooled glass. In addition, the equivalent cooling rate as a parameter reflecting the fictive temperature is too high, and as a result, the shrinkage of the glass cannot be reduced. Therefore, it is preferred to set R in such a way that the equivalent cooling rate becomes 800°C / minute or less. The equivalent cooling rate is more preferably less than 600°C / minute, further preferably less than 400°C / minute, further preferably less than 300°C / minute, further preferably less than 200°C / minute, particularly preferably less than 100°C / minute, more preferably less than 60°C / minute, and particularly preferably less than 40°C / minute. On the other hand, if the cooling rate is too small, the time required for the process is too long and the productivity becomes low. Therefore, it is preferably set to more than 0.1°C / minute, more preferably more than 0.5°C / minute, and more preferably more than 1°C / minute. From the perspective of the simplicity of evaluation, the equivalent cooling rate as a parameter reflecting the fictive temperature is preferably an equivalent cooling rate based on the refractive index.
[0343] Here, the definition and evaluation method of the equivalent cooling rate based on the refractive index are as follows. The glass of the composition to be the object is processed into a cube of 10mm×10mm×0.3~2.0mm to make a glass sample. The glass sample is heated by an infrared electric furnace and maintained at the strain point +170℃ for 5 minutes, and then the glass sample is cooled to room temperature (25℃). At this time, the conditions are changed within the range of cooling rate of 1℃ / min to 1000℃ / min to make multiple glass samples.
[0344] The refractive index n of a plurality of glass samples in d-ray (wavelength 587.6 nm) was measured using a precision refractive index measuring device (e.g., KPR3000 manufactured by Shimadzu Instruments Co., Ltd.). d The determination can be carried out by the V-block method or the minimum deflection angle method. d Plotted against the logarithm of the cooling rate, we get n d Standard curve relative to the cooling rates above.
[0345] Next, the n of a glass with the same composition actually produced through the steps of melting, forming, cooling, etc. is measured by the above-mentioned measuring method. d . Use the above standard curve to find the n d The corresponding corresponding cooling rate (in this embodiment, it refers to the equivalent cooling rate).
[0346] The method for producing the glass plate of the present invention is not limited to the above method. For example, when producing the glass plate of the present invention, the glass may be formed into a plate by a press molding method in which molten glass is directly molded into a plate.
[0347] In addition, when manufacturing the glass plate of the present invention, in addition to the manufacturing method using a melting tank made of refractory materials, a crucible made of platinum or an alloy mainly composed of platinum (hereinafter referred to as a platinum crucible) can also be used as a melting tank or a clarification tank. When a platinum crucible is used, in the melting process, raw materials are prepared in a manner to form the composition of the obtained glass plate, and the platinum crucible containing the raw materials is heated in an electric furnace, preferably to about 1450 to 1750°C. A platinum stirrer is inserted and stirred for 1 to 3 hours to obtain molten glass.
[0348] In the forming step of the glass plate manufacturing process using a platinum crucible, the molten glass is poured onto a carbon plate or a mold frame, for example, to form a plate or a block. The slow cooling step is typically maintained at T g After being heated to about +50°C, the glass is cooled at a rate of about 1 to 10°C / min to near the strain point, and then cooled to room temperature at a cooling rate that does not leave any residual strain. After cutting and grinding into a predetermined shape, a glass plate is obtained. In addition, the cut glass plate can be made into a T gAfter heating to about +50℃, slowly cool to room temperature at a specified cooling rate. This can adjust the equivalent cooling rate of the glass.
[0349] The circuit substrate 1 using the glass plate of the present invention as the glass substrate 2 is suitable for high-frequency devices that process high-frequency signals, especially high-frequency signals exceeding 30 GHz, and further high-frequency signals with a frequency of more than 35 GHz. It can reduce the transmission loss of such high-frequency signals and improve the quality or strength of high-frequency signals.
[0350] The circuit substrate 1 using the glass plate of the present invention as the glass substrate 2 is suitable for high-frequency devices (electronic devices) such as semiconductor devices used in communication equipment such as mobile phones, smart phones, portable information terminals, and Wi-Fi machines, radar components such as surface acoustic wave (SAW) devices and radar transceivers, antenna components such as liquid crystal antennas and panel-type antennas, etc.
[0351] That is, the present invention relates to a panel-type antenna including the glass of the present invention in addition to a glass substrate for a high-frequency device including the glass of the present invention.
[0352] In addition, the glass of the present invention can be appropriately applied to other products for the purpose of reducing the transmission loss of high-frequency signals. That is, the present invention also relates to window glass, vehicle window glass, and cover glass for touch panels comprising the glass of the present invention.
[0353] The glass plate including the glass of the present invention can stably transmit and receive radio waves in a high frequency band and is not easily damaged or broken, so it is also suitable for window glass, vehicle window glass, and cover glass for touch panels. As vehicle window glass, for example, automatic driving vehicle window glass is more preferred.
[0354] Example
[0355] Hereinafter, examples will be described, but the present invention is not limited to these examples. Hereinafter, Examples 1 to 28 are examples, and Examples 29 to 31 are comparative examples.
[0356] Prepare glasses having the compositions shown in Examples 1 to 31 (expressed as molar % on an oxide basis). Glass plates are produced by a melting method using a platinum crucible. Raw materials such as silica sand are mixed in such a manner as to obtain glasses having the compositions shown in Examples 1 to 31, and a 400 g batch is prepared. The raw materials are placed in a platinum crucible and heated in an electric furnace at a temperature of 1650°C for 1 hour to melt them and prepare molten glass. During melting, a platinum stirrer is inserted into the platinum crucible and stirred for 1 hour to homogenize the glass. Furthermore, after heating at a temperature of 1700°C for 3 hours, the molten glass is poured onto a carbon plate and, after being formed into a plate, the plate-shaped glass is placed in a T g+50℃ in an electric furnace for 1 hour. Cool down the furnace to T at a cooling rate of 1℃ / min. g The glass was then cooled to -100°C and then cooled to room temperature. Thereafter, the glass was cut and polished to form a plate to obtain a glass plate.
[0357] For the glass plates of Examples 1 to 31, the relative dielectric constant at a frequency of 10 GHz, the dielectric loss tangent at a frequency of 10 GHz, the dielectric loss tangent at T2, T4, T g , average thermal expansion coefficient at 50-350°C, amount of glass component dissolved per unit surface area when immersed in an aqueous solution containing 7.7 mass % HNO3 and 6.5 mass % H2SO4 at 45°C for 170 seconds (acid resistance), amount of glass component dissolved per unit surface area when immersed in an aqueous solution containing 1.2 mass % KOH at 60°C for 30 minutes (alkali resistance), plate thickness, Abs-OH, ΔAbs-OH, Abs β-OH -Abs Base , Δ(Abs β-OH -Abs Base ) are shown in Tables 1 to 5. The values in parentheses in the tables are calculated values or estimated values, "-" means not measured, and "×" means that the denominator in the calculation formula is 0 and cannot be calculated.
[0358] The measuring methods of various physical properties are shown below.
[0359] (Relative dielectric constant, dielectric loss tangent)
[0360] The measurement was performed using a cavity resonator and a vector network analyzer according to the method specified in JIS R1641 (2007). The measurement frequency was 10 GHz, which is the resonance frequency of air in the cavity resonator.
[0361] (density)
[0362] The density of a glass block of about 20 g containing no bubbles was measured by the Archimedean method.
[0363] (Temperature T2)
[0364] The viscosity was measured using a rotational viscometer according to the method specified in ASTM C 965-96 (2017) and the measured viscosity was 10 2 dPa·s when the temperature T2 (℃).
[0365] (Temperature T4)
[0366] The viscosity was measured using a rotational viscometer according to the method specified in ASTM C 965-96 (2017) and the measured viscosity was 10 4 dPa·s at temperature T4 (℃).
[0367] (T g )
[0368] The measurement was performed by a thermal expansion method according to the method specified in JIS R3103-3 (2001).
[0369] (Surface devitrification temperature)
[0370] The glass was crushed and classified using a test sieve so that the particle size was in the range of 2 to 4 mm. The obtained cullet was ultrasonically cleaned in isopropyl alcohol for 5 minutes, washed with ion exchange water, dried, placed in a platinum dish, and heat treated for 17 hours in an electric furnace controlled at a constant temperature. The heat treatment temperature was set at 10°C intervals.
[0371] After the heat treatment, the glass was removed from the platinum dish, and the highest temperature at which crystals were precipitated and the lowest temperature at which crystals were not precipitated on the surface of the glass were observed using an optical microscope.
[0372] The highest temperature at which crystals are precipitated on the surface of the glass and the lowest temperature at which crystals are not precipitated are each measured once. In addition, when it is difficult to judge whether crystals are precipitated, the temperature may be measured twice.
[0373] The average value of the highest temperature at which crystals precipitated on the glass surface and the lowest temperature at which crystals did not precipitate was calculated and used as the surface devitrification temperature.
[0374] (Average thermal expansion coefficient)
[0375] The measurement was performed using a differential thermal expansion instrument according to the method specified in JIS R3102 (1995). The measurement temperature range was 50 to 350°C and the unit was expressed as ×10 -7 / K.
[0376] (Acid resistance)
[0377] A glass plate with a side of 31 to 36 mm and a thickness of 0.45 to 0.75 mm and mirror surfaces on both sides was used as a glass sample. The glass sample was immersed in an acid aqueous solution (7.7 mass % HNO3 + 6.5 mass % H2SO4, 45°C) for 170 seconds, and the amount of glass component dissolved per unit surface area (mg / cm 2 ). The weight before immersion is expressed as weight Before , the weight after immersion is expressed as weight After When the vertical and horizontal lengths of the glass sample before immersion are expressed as length and width respectively, and the thickness is expressed as thickness, the elution amount of the glass component per unit surface area is calculated by the following formula.
[0378]
[0379] (Alkali resistance)
[0380] A glass plate with a side of 31 to 36 mm and a thickness of 0.45 to 0.75 mm and mirror surfaces on both sides was prepared as a glass sample. The glass sample was immersed in an alkaline aqueous solution (1.2 mass % KOH, 60° C.) for 30 minutes, and the amount of glass component dissolved per unit surface area (mg / cm 2 ). The weight before immersion is expressed as weight Before , the weight after immersion is expressed as weight After When the vertical and horizontal lengths of the glass sample before immersion are expressed as length and width respectively, and the thickness is expressed as thickness, the elution amount of the glass component per unit surface area is calculated by the following formula.
[0381]
[0382] (Board thickness (mm))
[0383] The thickness was measured using a micrometer (“Coolant proof micrometer” Code No. 293 230 30 manufactured by Mitutoyo Corporation).
[0384] (Abs-OH、(Abs β-OH -Abs Base ))
[0385] After both surfaces of the glass sample were mirror-polished to form a glass plate with a thickness of 0.45 to 0.75 mm, the sample was analyzed by FT-IR at a wave number of 4000 to 2000 cm -1 The transmittance was measured within the range of 3846 cm -1 The transmittance at τ1(%) is set, and the wave number is 3700-3200cm -1 The minimum value of the transmittance at is defined as τ2(%), and Abs-OH is calculated by the following formula.
[0386] Abs-OH=log 10 (τ2 / 100) / log 10 (τ1 / 100)
[0387] (Abs β-OH -Abs Base ) is set to Abs β-OH =-log 10 (τ2 / 100), Abs Base =-log 10 (τ1 / 100), calculated by their difference.
[0388] (ΔAbs-OH)
[0389] The Abs-OH of a glass plate having a thickness of 0.45 to 0.75 mm was measured. The glass plate was left to stand at a temperature of 60°C and a relative humidity of 95%, and the Abs-OH of the glass plate was measured 90 hours after the start of the standing. The value obtained by subtracting the Abs-OH before the standing from the Abs-OH after the standing was calculated as ΔAbs-OH.
[0390] (Δ(Abs β-OH -Abs Base ))
[0391] Determine the (Abs) of glass plates with a thickness of 0.45 to 0.75 mm β-OH -Abs Base The glass plate was left to stand at a temperature of 60° C. and a relative humidity of 95%, and the glass plate's (Abs β-OH -Abs Base ), calculate the (Abs β-OH -Abs Base ) minus the value before resting (Abs β-OH -Abs Base ) is taken as the value of Δ(Abs β-OH -Abs Base ).
[0392] [Table 1]
[0393] Table 1
[0394] [mol %] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 <![CDATA[SiO2]]> 71.3 68.8 69.4 74.0 73.0 74.0 <![CDATA[Al2O3]]> 5.0 4.0 4.0 5.0 5.0 4.0 <![CDATA[B2O3]]> 18.4 22.9 22.5 18.0 18.0 18.0 MgO 3.5 0 0 2.2 3.2 3.2 CaO 0 3.0 3.0 0 0 0 SrO 1.0 0.5 1.0 0.8 0.8 0.8 BaO 0.5 0.5 0 0 0 0 <![CDATA[Li2O]]> 0 0 0 0 0 0 <![CDATA[Na2O]]> 0 0 0 0 0 0 <![CDATA[K2O]]> 0 0 0 0 0 0 Cl 0.28 0.30 0.20 - - - <![CDATA[SO3]]> 0.0078 0.0088 0.0016 - - - <![CDATA[Fe2O3]]> 0.0016 0.0014 0.0015 - - - <![CDATA[TiO2]]> 0 0 0 0 0 0 RO 5.0 4.0 4.0 3.0 4.0 4.0 <![CDATA[R2O]]> 0 0 0 0 0 0 <![CDATA[SiO2+B2O3]]> 89.7 91.7 91.8 92.0 91.0 92.0 <h2 style=";text-align:left;direction:ltr"><![CDATA[B2O3-(RO+R2 <h2 style=";text-align:left;direction:ltr"> O <h2 style=";text-align:left;direction:ltr"> -Al2O3)]]><h2 style=";text-align:left;direction:ltr"> 18.4 22.9 22.5 20.0 19.0 18.0 <![CDATA[Al2O3-RO]]> 0 0 0 2.0 1.0 0 <![CDATA[Al2O3×RO]]> 24.85 15.90 15.94 15.00 20.00 16.00 <![CDATA[Al2O3×R2O]]> 0 0 0 0 0 0 MgO+CaO 3.5 3.0 3.0 2.2 3.2 3.2 SrO+BaO 1.5 1.0 1.0 0.8 0.8 0.8 (MgO+CaO)-(SrO+BaO) 2.0 2.0 2.0 1.4 2.4 2.4 <![CDATA[((MgO+CaO)-(SrO+BaO)) / Al2O3]]> 0.40 0.50 0.50 0.28 0.48 0.60 <![CDATA[MgO / (MgO+Al2O3)]]> 0.41 0 0 0.31 0.39 0.44 <![CDATA[Na2O / R2O]]> × × × × × × (SrO+BaO) / (MgO+CaO) 0.43 0.33 0.33 0.36 0.25 0.25 Relative dielectric constant (10GHz) 4.19 4.13 4.10 4.05 4.09 4.04 Dielectric loss tangent (10GHz) 0.0018 0.0014 0.0012 0.0013 0.0015 0.0014 <![CDATA[Density (g / cm 3 )]]> - - - - - - <![CDATA[T2(℃)]]> (1861) (1810) (1819) (1911) (1888) (1915) <![CDATA[T4(℃)]]> (1376) (1316) (1332) (1419) (1408) (1420) <![CDATA[T g (℃)]]> 659 617 (587) (611) (613) (598) Surface devitrification temperature (℃) - - - - - - <![CDATA[Average coefficient of thermal expansion (×10 -7 / K)]]> 28.2 31.8 (28.3) (24.4) (25.0) (24.8) <![CDATA[Acid resistance (mg / cm 2 )]]> 0.002 0.014 0.021 (0.001) (0.003) (0.002) <![CDATA[Alkali resistance (mg / cm 2 )]]> 0.046 0.064 0.100 (0.025) (0.037) (0.030) Thickness(mm) 0.502 0.493 0.498 0.677 0.678 0.687 Moisture resistance (ΔAbs-OH) 0.31 1.26 0.75 0.05 0.12 0.08 Abs-OH 1.62 1.43 4.41 1.97 1.77 1.94 <![CDATA[Abs β-OH -Abs Base ]]> 0.034 0.024 0.176 0.060 0.047 0.058 <![CDATA[Δ(Abs β-OH -AbS Base )]]> 0.02 0.06 0.03 0.01 0.01 0.01
[0395] [Table 2]
[0396] Table 2
[0397] [mol %] Example 7 Example 8 Example 9 Example 10 Example 11 Example 12 <![CDATA[siO2]]> 71.9 70.9 71.0 73.9 70.0 75.9 <![CDATA[Al2O3]]> 4.0 5.0 5.0 5.0 4.0 0.5 <![CDATA[B2O3]]> 20.0 22.0 22.0 19.0 24.0 21.5 MgO 0 0 0 0 0 0 CaO 3.0 1.0 2.0 2.0 2.0 0 SrO 1.0 1.0 0 0 0 0 Bao 0 0 0 0 0 0 <![CDATA[Li2O]]> 0 0 0 0 0 0.8 <![CDATA[Na2O]]> 0 0 0 0 0 0.8 <![CDATA[K2O]]> 0 0 0 0 0 0.4 Cl 0.17 0.08 0.04 0.09 0.03 0.12 <![CDATA[SO3]]> 0.0064 0.0033 0.0028 0.0031 0.0038 0.0039 <![CDATA[Fe2O3]]> 0.0018 0.0017 0.0015 0.0014 0.0022 0.0014 <![CDATA[TiO2]]> 0 0 0 0 0 0 RO 4.0 2.0 2.0 2.0 2.0 0 <![CDATA[R2O]]> 0 0 0 0 0 2.0 <![CDATA[SiO2+B2O3]]> 91.8 92.9 93.0 92.9 94.0 97.4 <![CDATA[B2O3-(RO+R2O-Al2O3)]]> 20.0 25.0 25.0 22.0 26.0 20.0 <![CDATA[Al2O3-RO]]> 0 3.0 3.0 3.0 2.0 0.5 <![CDATA[Al2O3×RO]]> 15.94 9.98 9.99 9.98 7.99 0 <![CDATA[Al2O3×R2O]]> 0 0 0 0 0 1.00 MgO+CaO 3.0 1.0 2.0 2.0 2.0 0 SrO+BaO 1.0 1.0 0 0 0 0 (MgO+CaO)-(SrO+BaO) 2.0 0 2.0 2.0 2.0 0 <![CDATA[((MgO+CaO)-(SrO+BaO)) / Al2O3]]> 0.50 0 0.40 0.40 0.50 0 <![CDATA[MgO / (MgO+Al2O3)]]> 0 0 0 0 0 0 <![CDATA[Na2O / R2O]]> × × × × × 0.40 (SrO+BaO) / (MgO+CaO) 0.33 1.00 0 0 0 × Relative dielectric constant (10GHz) 4.12 4.03 4.00 4.02 3.96 3.87 Dielectric loss tangent (10GHz) 0.0013 0.0011 0.0011 0.0012 0.0013 0.0016 <![CDATA[Density (g / cm 3 )]]> - 2.17 2.16 2.17 2.14 - <![CDATA[T2(℃)]]> (1861) (1861) (1846) (1897) (1840) (1802) <![CDATA[T4(℃)]]> (1366) (1366) (1362) (1403) (1348) (1151) <![CDATA[T g (℃)]]> (598) (591) 643 670 584 (504) Surface devitrification temperature (℃) - Below 1350 Below 1350 Below 1250 Below 1250 - <![CDATA[Average coefficient of thermal expansion (×10 -7 / K)]]> (27.1) (25.9) 28.9 25.2 30.8 (27.6) <![CDATA[Acid resistance (mg / cm 2 )]]> 0.008 (0.003) 0.001 0.000 0.001 (0.000) <![CDATA[Alkali resistance (mg / cm 2 )]]> 0.054 (0.033) 0.029 0.021 0.034 (0.013) Thickness(mm) 0.483 0.650 0.680 0.694 0.678 0.705 Moisture resistance (ΔAbs-OH) 0.27 0.27 0.67 0.23 1.79 0.07 Abs-OH 4.43 1.89 1.61 1.47 3.65 4.30 <![CDATA[Abs β-OH -Abs Base ]]> 0.170 0.054 0.040 0.029 0.180 0.206 <![CDATA[Δ(Abs β-OH -Abs Base )]]> 0.02 0.02 0.04 0.01 0.13 0.02
[0398] [Table 3]
[0399] Table 3
[0400] [mol %] Example 13 Example 14 Example 15 Example 16 Example 17 Example 18 <![CDATA[SiO2]]> 74.9 74.9 74.9 74.9 71.0 72.0 <![CDATA[Al2O3]]> 0.5 0.50 0.50 0.50 4.0 5.0 <![CDATA[B2O3]]> 22.5 22.5 22.5 22.5 22.0 20.0 MgO 0 0 0 0 0 0 CaO 0 0 0 0 2.0 1.0 SrO 0 0 0 0 1.0 1.0 BaO 0 0 0 0 0 1.0 <![CDATA[Li2O]]> 0.8 0.8 0.8 0.8 0 0 <![CDATA[Na2O]]> 0.9 0.9 0.9 0.9 0 0 <![CDATA[K2O]]> 0.3 0.3 0.3 0.3 0 0 Cl 0.15 0.09 0.10 0.13 0 0 <![CDATA[SO3]]> 0.0078 0.0020 0.0060 0.0038 0 0 <![CDATA[Fe2O3]]> 0.0011 0.0016 0.0011 0.0009 0 0 <![CDATA[TiO2]]> 0 0 0 0 0 0 RO 0 0 0 0 3.0 3.0 <![CDATA[R2O]]> 2.0 2.0 2.0 2.0 0 0 <![CDATA[siO2+B2O3]]> 97.3 97.3 97.3 97.3 93.0 92.0 <![CDATA[B2O3-(RO+R2O-Al2O3)]]> 21.0 21.0 21.0 21.0 23.0 22.0 <![CDATA[Al2O3-RO]]> 0.5 0.5 0.5 0.5 1.0 2.0 <![CDATA[Al2O3×RO]]> 0 0 0 0 12.0 15.0 <![CDATA[Al2O3×R2O]]> 1.00 1.00 1.00 1.00 0 0 MgO+CaO 0 0 0 0 2.0 1.0 SrO+BaO 0 0 0 0 1.0 2.0 (MgO+CaO)-(SrO+BaO) 0 0 0 0 1.0 -1.0 <![CDATA[((MgO+CaO)-(SrO+BaO)) / Al2O3]]> 0 0 0 0 0.25 -0.20 <![CDATA[MgO / (MgO+Al2O3)]]> 0 0 0 0 0 0 <![CDATA[Na2O / R2O]]> 0.45 0.45 0.45 0.45 × × (SrO+BaO) / (MgO+CaO) × × × × × × Relative dielectric constant (10GHz) 3.84 3.89 3.88 3.87 (4.06) (4.16) Dielectric loss tangent (10GHz) 0.0014 0.0014 0.0015 0.0014 (0.0010) (0.0012) <![CDATA[Density (g / cm 3 )]]> - - - - - - <![CDATA[T2(℃)]]> (1800) - - - (1858) (1876) <![CDATA[T4(℃)]]> (1135) - - - (1359) (1358) <![CDATA[T g (℃)]]> (499) - - - (583) (598) Surface devitrification temperature (℃) - - - - - v <![CDATA[Average coefficient of thermal expansion (×10 -7 / K)]]> (27.9) - - - (26.8) (26.5) <![CDATA[Acid resistance (mg / cm 2 )]]> (0.000) - - - (0.001) (0.001) <![CDATA[Alkaline resistance (mg / cm 2 )]]> (0.016) - - - (0.071) (0.057) Thickness(mm) 0.684 0.6762 0.692 0.6832 - - Moisture resistance (ΔAbs-OH) 0.99 - - - (0.95) (0.40) Abs-OH 4.26 - - - - - <![CDATA[Abs β-OH -Abs Base ]]> 0.206 - - - - - <![CDATA[Δ(Abs β-OH -Abs Base )]]> 0.04 - - - (0~0.05) (0~0.05)
[0401] [Table 4]
[0402] Table 4
[0403] [mol %] Example 19 Example 20 Example 21 Example 22 Example 23 Example 24 <![CDATA[SiO2]]> 71.0 74.0 70.0 70.0 77.0 74.0 <![CDATA[Al2O3]]> 5.0 4.0 4.0 3.0 0.3 0.3 <![CDATA[B2O3]]> 22.0 20.0 24.0 24.0 20.5 23.5 MgO 0 0 0 0.5 0 0 CaO 1.0 1.0 1.0 1.0 0 0 SrO 1.0 1.0 1.0 1.0 0 0 BaO 0 0 0 0.5 0 0 <![CDATA[Li2O]]> 0 0 0 0 1.0 1.0 <![CDATA[Na2O]]> 0 0 0 0 1.0 0.9 <![CDATA[K2O]]> 0 0 0 0 0.2 0.3 Cl 0 0 0 0 0 0 <![CDATA[SO3]]> 0 0 0 0 0 0 <![CDATA[Fe2O3]]> 0 0 0 0 0 0 <![CDATA[TiO2]]> 0 0 0 0 0 0 RO 2.0 2.0 2.0 3.0 0 0 <![CDATA[R2O]]> 0 0 0 0 2.2 2.2 <![CDATA[SiO2+B2O3]]> 93.0 94.0 94.0 94.0 97.5 97.5 <![CDATA[B2O3-(RO+R2O-Al2O3)]]> 25.0 22.0 26.0 24.0 18.6 21.6 <![CDATA[Al2O3-RO]]> 3.0 2.0 2.0 0 0.3 0.3 <![CDATA[Al2O3×RO]]> 10.0 8.0 8.0 9.0 0 0 <![CDATA[Al2O3×R2O]]> 0 0 0 0 0.66 0.66 MgO+CaO 1.0 1.0 1.0 1.5 0 0 SrO+BaO 1.0 1.0 1.0 1.5 0 0 (MgO+CaO)-(SrO+BaO) 0 0 0 0 0 0 <![CDATA[((MgO+CaO)-(SrO+BaO)) / Al2O3]]> 0 0 0 0 0 0 <![CDATA[MgO / (MgO+Al2O3)]]> 0 0 0 0 0 0 <![CDATA[Na2O / R2O]]> × × × × 0.45 0.41 (SrO+BaO) / (MgO+CaO) × × × × × × Relative dielectric constant (10GHz) (4.02) (4.06) (3.96) (4.00) (3.98) (3.92) Dielectric loss tangent (10GHz) (0.0010) (0.0010) (0.0009) (0.0009) (0.0018) (0.0016) <![CDATA[Density (g / cm 3 )]]> - - - - - - <![CDATA[T2(℃)]]> (1861) (1921) (1854) (1860) - - <![CDATA[T4(℃)]]> (1366) (1406) (1351) (1341) - - <![CDATA[T g (℃)]]> (591) (605) (567) (551) (497) (488) Surface devitrification temperature (℃) - - - - - - <![CDATA[Average coefficient of thermal expansion (×10 -7 / K)]]> (25.9) (24.7) (26.7) (27.5) (27.4) (28.7) <![CDATA[Acid resistance (mg / cm 2 )]]> (0.001) (0.000) (0.001) (0.002) (0.000) (0.000) <![CDATA[Alkali resistance (mg / cm 2 )]]> (0.057) (0.033) (0.071) (0.089) (0.022) (0.039) Thickness(mm) - - - - - - Moisture resistance (ΔAbs-OH) (0.77) (0.45) (1.33) (1.51) (0.21) (0.87) Abs-OH - - - - - - <![CDATA[Abs β-OH -Abs Base ]]> - - - - - - <![CDATA[Δ(Abs β-OH -Abs Base )]]> (0~0.05) (0~0.05) (0~0.1) (0~0.1) (0~0.05) (0~0.1)
[0404] [Table 5]
[0405] Table 5
[0406] [mol %] Example 25 Example 26 Example 27 Example 28 Example 29 Example 30 Example 31 <![CDATA[SiO2]]> 76.8 75.8 75.8 75.0 59.7 64.4 68.0 <![CDATA[Al2O3]]> 0.4 0.4 0.4 0.2 4.0 4.0 4.0 <![CDATA[B2O3]]> 21.0 22.0 22.0 23.0 30.0 27.4 26.0 MgO 0 0 0 0 3.2 0 0 CaO 0 0 0 0 0 3.0 2.0 SrO 0 0 0 0 0.8 1.0 0 BaO 0 0 0 0 0.2 0 0 <![CDATA[Li2O]]> 0.4 0.9 0.4 0.7 0 0 0 <![CDATA[Na2O]]> 1.2 0.6 1.0 0.8 0 0 0 <![CDATA[K2O]]> 0.2 0.3 0.4 0.3 0 0 0 Cl 0 0 0 0 0.10 0.19 0.03 <![CDATA[SO3]]> 0 0 0 0 0.0070 0.0035 0.0038 <![CDATA[Fe2O3]]> 0 0 0 0 0.0028 0.0015 0.0015 <![CDATA[TiO2]]> 0 0 0 0 2.0 0 0 RO 0 0 0 0 4.2 4.0 2.0 <![CDATA[R2O]]> 1.8 1.8 1.8 1.8 0 0 0 <![CDATA[SiO2+B2O3]]> 97.8 97.8 97.8 98.0 89.7 91.8 94.0 <![CDATA[B2O3-(RO+R2O-Al2O3)]]> 19.6 20.6 20.6 21.4 29.8 27.4 28.0 <![CDATA[Al2O3-RO]]> 0.4 0.4 0.4 0.2 -0.2 0 2.0 <![CDATA[Al2O3×RO]]> 0 0 0 0 16.8 15.9 8.0 <![CDATA[Al2O3×R2O]]> 0.72 0.72 0.72 0.36 0 0 0 MgO+CaO 0 0 0 0 3.2 3.0 2.0 SrO+BaO 0 0 0 0 1.0 1.0 0 (MgO+CaO)-(SrO+BaO) 0 0 0 0 2.2 2.0 2.0 <![CDATA[((MgO+CaO)-(SrO+BaO)) / Al2O3]]> 0 0 0 0 0.55 0.50 0.50 <![CDATA[MgO / (MgO+Al2O3)]]> 0 0 0 0 0 0 0 <![CDATA[Na2O / R2O]]> 0.67 0.33 0.56 0.44 × × × (SrO+BaO) / (MgO+CaO) × × × × × × × Relative dielectric constant (10GHz) (3.95) (3.90) (3.93) (3.89) 4.09 4.07 3.96 Dielectric loss tangent (10GHz) (0.0021) (0.0012) (0.0019) (0.0015) 0.0013 0.0011 0.0012 <![CDATA[Density (g / cm 3 )]]> - - - - - - - <![CDATA[T2(℃)]]> - - - - (1696) (1735) (1806) <![CDATA[T4(℃)]]> - - - - (1239) (1264) (1321) <![CDATA[T g (℃)]]> (507) (502) (506) (493) (575) (567) 569 Surface devitrification temperature (℃) - - - - - - - <![CDATA[Average coefficient of thermal expansion (×10 -7 / K)]]> (26.8) (27.2) (27.5) (27.9) (29.4) (31.2) 32.1 <![CDATA[Acid resistance (mg / cm 2 )]]> (0.000) (0.000) (0.000) (0.000) - 0.058 0.002 <![CDATA[Alkali resistance (mg / cm 2 )]]> (0.021) (0.026) (0.026) (0.030) - 0.160 0.043 Thickness(mm) - - - - 0.495 0.483 0.691 Moisture resistance (ΔAbs-OH) (0.43) (0.65) (0.65) (0.89) 7.22 4.44 7.62 Abs-OH - - - - 3.93 4.49 3.98 <![CDATA[Abs β-OH -AbS Base ]]> - - - - 0.178 0.185 0.209 <![CDATA[Δ(Abs β-OH -Abs Base )]]> (0~0.05) (0~0.1) (0~0.05) (0~0.05) 0.48 0.24 0.62
[0407] In Examples 1 to 8 and 17 to 22, where SrO is 0.1 to 4%, [Al2O3]×[RO] is greater than 0 and less than 30, [MgO]+[CaO] is 0.1 to 5.9, and [MgO] / ([MgO]+[Al2O3]) is 0 to 0.45, the relative dielectric constant at a frequency of 10 GHz is less than 4.5, the dielectric loss tangent at a frequency of 10 GHz is less than 0.005, and the acid resistance is 0.05 mg / cm 2 Below, 0.15mg / cm in alkali resistance evaluation 2 Below, ΔAbs-OH is below 4.0, Δ(Abs β-OH -Abs Base ) is less than 0.2.
[0408] In Examples 2 to 3, 7 to 11, and 17 to 22, where CaO is 0.1 to 6%, [Al2O3]×[RO] is greater than 0 and less than 28, and (([MgO]+[CaO])-([SrO]+[BaO])) / [Al2O3] is -3.0 to 0.60, the relative dielectric constant at a frequency of 10 GHz is less than 4.5, the dielectric loss tangent at a frequency of 10 GHz is less than 0.005, and the acid resistance is 0.05 mg / cm 2 Below, 0.15mg / cm in alkali resistance evaluation 2 Below, ΔAbs-OH is below 4.0, Δ(Abs β-OH -Abs Base ) is less than 0.2.
[0409] In Examples 12 to 13 and Examples 23 to 28, where Li2O is greater than 0%, K2O is greater than 0% and less than 0.8%, R2O is greater than 0% and less than 4%, [Al2O3]×[R2O] is greater than 0 and less than 1.40, and [Na2O] / [R2O] is 0.30 to 0.99, the relative dielectric constant at a frequency of 10 GHz is less than 4.5, the dielectric loss tangent at a frequency of 10 GHz is less than 0.005, and the acid resistance is 0.05 mg / cm 2 Below, 0.15mg / cm in alkali resistance evaluation 2 Below, ΔAbs-OH is below 4.0, Δ(Abs β-OH -Abs Base ) is less than 0.2.
[0410] In Example 29, where SiO2 is less than 68% and [B2O3]-([RO]+[R2O]-[Al2O3]) is greater than 27%, ΔAbs-OH and Δ(Absβ-OH -Abs Base ) is larger than that of the embodiment and has poor moisture resistance.
[0411] Compared with the examples, the ΔAbs-OH and Δ(Abs β-OH -Abs Base ) is large, and moisture resistance is poor. In addition, acid and alkali resistance are also poor.
[0412] In Example 31, where [B2O3]-([RO]+[R2O]-[Al2O3]) was greater than 27%, ΔAbs-OH and Δ(Abs β-OH -Abs Base ) is larger than that of the embodiment and has poor moisture resistance.
[0413] Figure 2 This is a graph showing the relationship between [B2O3]-([RO]+[R2O]-[Al2O3]) and ΔAbs-OH, and the results of Examples 1 to 13 and Examples 26 to 28 are plotted. Figure 2 As shown, it can be seen that as [B2O3]-([RO]+[R2O]-[Al2O3]) increases, the moisture resistance of the glass deteriorates. In addition, if [B2O3]-([RO]+[R2O]-[Al2O3]) is greater than 27%, ΔAbs-OH becomes significantly larger. Since the glass of the present invention has [B2O3]-([RO]+[R2O]-[Al2O3]) of less than 27%, ΔAbs-OH is low, indicating that the glass has excellent moisture resistance.
[0414] Figure 3 : is a graph showing the relationship between the Cl content and Abs-OH in the glasses of Examples 13 to 16. Figure 3 As shown in FIG. 1 , it is observed that as the Cl content in the glass increases, the Abs-OH decreases. Figure 4 This is a graph showing the relationship between the relative dielectric constant and dielectric loss tangent of Abs-OH of Examples 13 to 16 at a frequency of 10 GHz. Figure 4 As shown in the figure, as the Abs-OH decreases, the relative dielectric constant and dielectric loss tangent decrease, and the dielectric properties improve. Therefore, it is shown that the dielectric properties are improved by adding Cl.
[0415] While the present invention has been described in detail and with reference to specific embodiments, it will be apparent to one skilled in the art that various changes and modifications can be added without departing from the spirit and scope of the present invention.
[0416] Industrial Applicability
[0417] The surface devitrification temperature of the glass of the present invention is low, and the chemical resistance and moisture resistance are excellent, and the dielectric loss of high-frequency signals can be reduced. The glass plate comprising such glass is useful in processing high-frequency signals above 10GHz, particularly high-frequency signals above 30GHz, and further all high-frequency electronic devices of high-frequency signals above 35GHz, such as glass substrates of communication machines (antenna modules required in wireless communication, substrates used in high-frequency passive components, etc.), frequency filter components such as SAW devices and FBAR, bandpass filters such as waveguides, SIW (Substrate integrated waveguide) components, radar components, antenna components (most suitable for liquid crystal antennas for satellite communications, etc.), window glass, vehicle window glass, display panels, etc.
[0418] The present invention is described in detail with reference to a specific mode, but it is clear to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. It should be noted that this application is based on the Japanese patent application (Japanese Patent Application No. 2022-077216) filed on May 9, 2022, and is cited in its entirety by reference. In addition, all references cited herein are introduced into this specification as a whole.
[0419] Explanation of symbols
[0420] 1: Circuit board
[0421] 2: Glass substrate
[0422] 2a, 2b: Main surface
[0423] 3, 4: Wiring layer
Claims
1. A glass, expressed in mole % based on oxides, SiO2 is more than 68%, Al2O3 is 0.1~8%, [SiO2]+[B2O3] is more than 88%, [B2O3]-([RO]+[R2O]-[Al2O3]) is less than 27%, The relative dielectric constant at 25°C and 10 GHz is less than 4.
5. The dielectric loss tangent at 25°C and 10 GHz is less than 0.
005. ΔAbs-OH calculated by the following method is 4.0 or less, SrO is 0.1-4%, The total content (RO) of MgO, CaO, SrO and BaO is greater than 0% and less than 6%, The total content of Li2O, Na2O and K2O (R2O) is 0-1%. [Al2O3]-[RO] is greater than -3% and less than 8%, [Al2O3]×[RO] is greater than 0 and less than 30, [MgO] + [CaO] is 0.1 to 5.9%, [MgO] / ([MgO]+[Al2O3]) is 0 to 0.45, [] indicates the content of the component in brackets expressed as mol % based on oxide. The method comprises the following steps: making the glass into a glass plate with a thickness of 0.45 to 0.75 mm, measuring Abs-OH, and then leaving the glass plate to stand at a temperature of 60° C. and a relative humidity of 95%. 90 hours after the start of the standing, the Abs-OH of the glass plate is measured, and the value obtained by subtracting the Abs-OH before the standing from the Abs-OH after the standing is calculated as ΔAbs-OH.
2. A glass, expressed in mole % based on oxides, SiO2 is more than 68%, Al2O3 is 0.1~8%, [SiO2]+[B2O3] is more than 88%, [B2O3]-([RO]+[R2O]-[Al2O3]) is less than 27%, The relative dielectric constant at 25°C and 10 GHz is less than 4.
5. The dielectric loss tangent at 25°C and 10 GHz is less than 0.
005. ΔAbs-OH calculated by the following method is 4.0 or less, CaO is 0.1-6%, The total content (RO) of MgO, CaO, SrO and BaO is greater than 0% and less than 6%, The total content of Li2O, Na2O and K2O (R2O) is 0-1%. [Al2O3]-[RO] is greater than -3% and less than 8%, [Al2O3]×[RO] is greater than 0 and less than 28, (([MgO]+[CaO])-([SrO]+[BaO])) / [Al2O3] is -3.0~0.60, [] indicates the content of the component in brackets expressed as mol % based on oxide. The method comprises the following steps: making the glass into a glass plate with a thickness of 0.45 to 0.75 mm, measuring Abs-OH, and then leaving the glass plate to stand at a temperature of 60° C. and a relative humidity of 95%. 90 hours after the start of the standing, the Abs-OH of the glass plate is measured, and the value obtained by subtracting the Abs-OH before the standing from the Abs-OH after the standing is calculated as ΔAbs-OH.
3. A glass, expressed in mole % based on oxides, SiO2 is more than 68%, Al2O3 is 0.1~8%, [SiO2]+[B2O3] is more than 88%, [B2O3]-([RO]+[R2O]-[Al2O3]) is less than 27%, The relative dielectric constant at 25°C and 10 GHz is less than 4.
5. The dielectric loss tangent at 25°C and 10 GHz is less than 0.
005. ΔAbs-OH calculated by the following method is 4.0 or less, Li2O is greater than 0%, K2O is greater than 0% and less than 0.8%, The total content of MgO, CaO, SrO and BaO (RO) is 0-0.5%, The total content of Li2O, Na2O and K2O (R2O) is greater than 0% and less than 4%, [Al2O3]×[R2O] is greater than 0 and less than 1.40, [Na2O] / [R2O] is 0.30 to 0.99, [] indicates the content of the component in brackets expressed as mol % based on oxide. The method comprises the following steps: making the glass into a glass plate with a thickness of 0.45 to 0.75 mm, measuring Abs-OH, and then leaving the glass plate to stand at a temperature of 60° C. and a relative humidity of 95%. 90 hours after the start of the standing, the Abs-OH of the glass plate is measured, and the value obtained by subtracting the Abs-OH before the standing from the Abs-OH after the standing is calculated as ΔAbs-OH.
4. The glass according to any one of claims 1 to 3, wherein The acid resistance calculated by the following method is 0.05 mg / cm 2 Below, alkali resistance is 0.15mg / cm 2 the following, The acid resistance evaluation method is as follows: the glass is made into a glass plate with a side of 31 to 36 mm and a thickness of 0.45 to 0.75 mm, and the glass plate is immersed in an acid aqueous solution for 170 seconds, and the amount of glass component dissolved per unit surface area is calculated as the acid resistance. The acid aqueous solution is a 45°C aqueous solution containing 7.7 mass % HNO3 and 6.5 mass % H2SO4, and the unit of the dissolved amount is mg / cm 2 , The evaluation method of the alkali resistance is as follows: the glass is made into a glass plate with a side of 31 to 36 mm and a thickness of 0.45 to 0.75 mm, and the glass plate is immersed in an alkaline aqueous solution for 30 minutes, and the elution amount of the glass component per unit surface area is calculated as the alkali resistance. The alkaline aqueous solution is a 60°C aqueous solution containing 1.2 mass% KOH, and the unit of the elution amount is mg / cm 2 .
5. The glass according to any one of claims 1 to 3, wherein In terms of mol % based on oxides, 0.01% or more of Cl is contained.
6. The glass according to any one of claims 1 to 3, wherein Abs-OH is 0.1~10.
7. The glass according to any one of claims 1 to 3, wherein The average thermal expansion coefficient at 50-350°C is 20×10 -7 / K~50×10 -7 / K.
8. The glass according to any one of claims 1 to 3, wherein The glass transition temperature is 750°C or lower. 9 . A glass plate comprising the glass according to claim 1 , having a main surface and an end surface, and having a thickness of 0.75 mm or less. 10 . A method for producing a glass plate, comprising producing the glass according to claim 1 by a float process or a fusion process. 11 . A glass substrate comprising the glass according to claim 1 , the glass substrate being used for a high-frequency device that processes a high-frequency signal of 10 GHz or more.
12. A glass substrate comprising the glass according to any one of claims 1 to 3, A wiring layer is formed on the glass substrate.
Citation Information
Cited By
Production process of anti-microcrack and anti-edge-breakage tempered glass
CN120553999A
A production process of anti-micro crack and edge collapse reinforced glass
CN120553999B
